Aqueous composition, dilution composition, and aqueous coating composition

By using a combination of block copolymers with a specific structure and water, the problem of insufficient hydrophilicity of viscosity adjusters in existing water-based paints is solved, and effective viscosity imparted to water is achieved and the sagging and leveling properties of the paint are improved. .

CN119365517APending Publication Date: 2025-01-24KUSUMOTO CHEM
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380044921.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The viscosity adjusting agent in existing water-based coatings has insufficient hydrophilicity, which makes it difficult to effectively impart viscosity in water. It is restricted by regulations, and the amount and type of organic solvents used are limited, making it difficult to meet viscosity requirements.

Method used

A block copolymer containing a carboxyl group at the molecular end and a specific structure of a polyamide block and a polyether block is used as a viscosity modifier. When used in combination with water, the viscosity of water is increased, and in conventional compositions The viscosity-imparting effect can be fully exerted even in formulations where the effect is difficult to exert.

Benefits of technology

Effectively gives viscosity to water, enhance the viscosity of water coating, and the viscosity effect that is difficult to achieve in traditional compositions can also be realized, which improves the flowing and flat performance of coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169376120000251
    Figure BDA0005169376120000251
  • Figure BDA0005169376120000261
    Figure BDA0005169376120000261
  • Figure BDA0005169376120000262
    Figure BDA0005169376120000262
Patent Text Reader

Abstract

Provided are an aqueous composition, a dilution composition, and an aqueous coating composition which are capable of imparting stickiness to water and which are capable of exhibiting a sufficient stickiness imparting effect even when blended in conventional compositions which are difficult to exhibit the stickiness imparting effect. The aqueous composition contains water and a block copolymer (A1) represented by (X-) a [R1 (-W1-R2-W2) b] m (-R1 (-X) c) p, among all X in the block copolymer (A1) represented by formula (1), X, which is Y, is 5 mol% or more, and A1 / water, which is the mass ratio of the block copolymer (A1) to water, is 5 / 95 to 50 / 50.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aqueous composition, a diluted composition and a water-based coating composition. Background Art

[0002] Water-based paint is a paint that responds to environmental protection, so water-based paint is being promoted in various fields, including automotive paint. Various viscosity adjusters are used in these water-based paints, for example, to prevent the sedimentation and hardening of pigments in the paint during storage, to prevent the paint from dripping during painting, and to adjust the leveling of the painted surface.

[0003] As such a viscosity modifier, for example, Patent Document 1 discloses a water-based coating anti-settling agent composed of a polyamide obtained by reacting a diamine with an excess of a dicarboxylic acid relative to the diamine, etc., neutralized with a neutralizing base (amine, etc.), and then dispersed in a medium mainly composed of water. In addition, Patent Document 2 discloses a composition composed of a hydrocarbon-polyether-polyamide-polyether-hydrocarbon block polymer and a specific solvent as a gelling agent for urethane / acrylic coatings.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 10-310726

[0007] Patent Document 2: Japanese Patent Application No. 2004-518006 Summary of the invention

[0008] Technical Problems to be Solved by the Invention

[0009] However, in the sedimentation inhibitor recorded in patent documentation 1, only the carboxylic acid at the end is the hydrophilic part, so the hydrophilicity of polyamide is not enough, and the situation that needs a large amount of cosolvents to give effect in order to bring into play viscosity is more.On the other hand, the amount of organic solvent released in the environment and the influence of available organic solvent types being restricted by laws and regulations exist that the amount of organic solvent in water-based coating, type and resin adopt different designs from the past.Therefore, in some cases, it is difficult to give viscosity to the few allotment of cosolvents and allotment without cosolvents or water itself that considers laws and regulations in recent years by the sedimentation inhibitor recorded in patent documentation 1.In addition, there is the situation of poor hydrophilicity in the gel recorded in patent documentation 2, and the situation of dispersion difficulty relative to the allotment of water system is more, even if it can be dispersed in water, when adjusting with viscosity as the purpose, the viscosity of the allotment of water and other water systems gives effect weakly, and the situation that cannot become sufficient viscosity is more.

[0010] Therefore, the present invention is proposed in view of the above situation, and its purpose is to provide an aqueous composition that can impart viscosity to water and can exert a sufficient viscosity imparting effect even in a formulation that is difficult to exert the viscosity imparting effect in conventional compositions, as well as a diluted composition and a water-based coating composition containing the aqueous composition.

[0011] Technical solutions for solving technical problems

[0012] The present inventors have conducted intensive studies in order to solve the above-mentioned technical problems and have found that by using an aqueous composition containing a block copolymer having a specific structure of a polyamide block and a polyether block and having a carboxyl group at a molecular terminal and water as a viscosity modifier, viscosity can be imparted to water, and that a sufficient viscosity imparting effect can be exerted even in a composition that has been difficult to exert a viscosity imparting effect in the past. The present invention has been completed based on this finding.

[0013] That is, the present invention is an aqueous composition characterized in that it contains: a block copolymer (A1) represented by the following general formula (1), and water, wherein among all X in the block copolymer (A1) represented by the formula (1), X as Y accounts for 5 mol% or more, and the mass ratio of the block copolymer (A1) to water, i.e., A1 / water, is 5 / 95 to 50 / 50.

[0014] (X-) a [R1(-W1-R2-W2) b ] m (-R1(-X) c ) p (1)

[0015] (In the formula (1), X is independently a carboxyl group or a salt thereof, or Y, and Y is R3-(OR4) n -Z-, R1 is independently a divalent and / or trivalent hydrocarbon group having 2 to 52 carbon atoms, R2 is a divalent hydrocarbon group having 2 to 36 carbon atoms, R3 is a hydrocarbon group having 1 to 22 carbon atoms, R4 is a divalent hydrocarbon group having 2 to 4 carbon atoms, W1 and W2 are secondary amide bonds, Z is an ester bond or an amide bond, a is an integer of 1 to 11, b is 1 or 2, c is 1 or 2, m is an integer of 0 to 10, n is an integer of 2 to 100, and p is an integer of 1 to 11.)

[0016] In one embodiment of the present invention, the aqueous composition may contain the block copolymer (A1) in which at least a part of X in the formula (1) is a carboxyl group or a salt thereof.

[0017] In another embodiment of the present invention, X which is a carboxyl group or a salt thereof may account for 30 mol% or more based on the entire amount of X in the block copolymer (A1) contained in the aqueous composition.

[0018] In another embodiment of the present invention, the remaining mass after removing the Y portion from all the block copolymers (A1) contained in the aqueous composition may be 50% by mass or more and 90% by mass or less based on the total mass of the block copolymer (A1).

[0019] In another embodiment of the present invention, the acid value of the block copolymer (A1) may be 15 or more and 80 or less.

[0020] In another embodiment of the present invention, 50 mol % or more of either or both of R1 and R2 in the formula (1) may be a divalent hydrocarbon group having 34 or more carbon atoms.

[0021] In another embodiment of the present invention, at least a part of X in the formula (1) may be Y, and R4 has 2 carbon atoms (OR4) n The mass of the site is 5 mass% to 45 mass% based on the mass of the entire block copolymer (A1).

[0022] In another embodiment of the present invention, the aqueous composition may further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), wherein at least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has a carbon number of 2 (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5 mass% or more and 50 mass% or less based on the total mass of the block copolymer (A1) and the polyether (B1).

[0023] R5-(OR6) q -OR7…(2)

[0024] (In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100.)

[0025] In another embodiment of the present invention, the aqueous composition may further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), wherein at least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has a carbon number of 2 (OR4) nsite, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5 mass % or more and 50 mass % or less with respect to the total mass of the nonvolatile content in the aqueous composition.

[0026] R5-(OR6) q -OR7…(2)

[0027] (In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100.)

[0028] In another embodiment of the present invention, the aqueous composition may contain the block copolymer (A1) in which all Xs in the formula (1) are Ys.

[0029] In another embodiment of the present invention, X as Y in X in the block copolymer (A1) represented by the formula (1) may account for 80 mol% or more.

[0030] In another embodiment of the present invention, the aqueous composition may further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), and the acid value of the mixture of the block copolymer (A1) and the polyether (B1) is 10 or less.

[0031] R5-(OR6) q -OR7…(2)

[0032] (In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100.)

[0033] In another embodiment of the present invention, the number of carbon atoms of R3 in the formula (1) may be 1 to 4.

[0034] In another embodiment of the present invention, the block copolymer (A1) in which m=0 in the formula (1) may account for 50% by mass or less based on the total mass of the block copolymer (A1) contained in the aqueous composition.

[0035] In another embodiment of the present invention, the aqueous composition may further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), wherein at least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has a carbon number of 2 (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6)q The total mass of the sites is 50% by mass or more and 90% by mass or less based on the total mass of the block copolymer (A1) and the polyether (B1).

[0036] R5-(OR6) q -OR7…(2)

[0037] (In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100.)

[0038] In another embodiment of the present invention, the aqueous composition may further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), wherein at least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has a carbon number of 2 (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the parts may be 50% by mass or more and 90% by mass or less relative to the total mass of the nonvolatile content in the aqueous composition.

[0039] R5-(OR6) q -OR7…(2)

[0040] (In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100.)

[0041] The present invention also provides a diluted composition obtained by diluting the above aqueous composition, wherein the mass ratio of the block copolymer (A1) to water, i.e., A1 / water, is 0.01 / 99.99 to 5 / 95.

[0042] The diluted composition may further contain at least one viscosity modifier which is different from the block copolymer (A1) and is selected from the group consisting of urethane viscosity modifiers, acrylic viscosity modifiers, modified cellulose viscosity modifiers, polysaccharide viscosity modifiers, amide viscosity modifiers, polyamide viscosity modifiers, urea viscosity modifiers, cellulose nanofibers, and inorganic viscosity modifiers.

[0043] In one embodiment of the present invention, there is provided a water-based coating composition comprising the above-mentioned water-based composition and a bright pigment.

[0044] The water-based coating composition may further contain at least one viscosity modifier which is different from the block copolymer (A1) and is selected from the group consisting of a carbamate viscosity modifier, an acrylic viscosity modifier, a cellulose modified substance viscosity modifier, a polysaccharide viscosity modifier, an amide viscosity modifier, a polyamide viscosity modifier, a urea viscosity modifier, cellulose nanofibers, and an inorganic viscosity modifier.

[0045] Effects of the Invention

[0046] According to the present invention, by using a block copolymer having a specific structure of a polyamide block and a polyether block and water as a viscosity modifier, it is possible to impart viscosity to water, and even a sufficient viscosity imparting effect can be exerted even in a composition that is difficult to exert a viscosity imparting effect in the past. In addition, according to the present invention, it is also possible to exert a dispersion effect of pigments in water-based coatings by adjusting the blending when synthesizing the block copolymer. DETAILED DESCRIPTION

[0047] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0048] [Aqueous composition]

[0049] The aqueous composition of the present invention is an additive for a water-based coating composition, and contains a block copolymer (A1) represented by the following general formula (1) and water.

[0050] (X-) a [R1(-W1-R2-W2) b ] m (-R1(-X) c ) p …(1)

[0051] (Block copolymer (A1))

[0052] In the above formula (1), X is independently a carboxyl group or a salt thereof, or Y. Y is R3-(OR4) n -Z-. R1 is independently a divalent and / or trivalent hydrocarbon group having 2 to 52 carbon atoms. R2 is a divalent hydrocarbon group having 2 to 36 carbon atoms. R3 is a hydrocarbon group having 1 to 22 carbon atoms. R4 is a divalent hydrocarbon group having 2 to 4 carbon atoms. W1 and W2 are secondary amide bonds. Z is an ester bond or an amide bond. a is an integer of 1 to 11. b is 1 or 2. c is 1 or 2. m is an integer of 0 to 10. n is an integer of 2 to 100. p is an integer of 1 to 11.

[0053] Here, [R1(-W1-R2-W2) in formula (1) b ]m There are m R1s in the formula, and each of them can be divalent or trivalent. b ] m One of R1 in [R1(-W1-R2-W2) b ] m One of them is bonded to the outer atom of and the other is bonded to W1. However, when R1 is trivalent, there are two types of bonds: one is further bonded to X or the other is bonded to W1. For example, in formula (1), when m=1, [R1(-W1-R2-W2) b ] m There is one R1 in the formula (1), and the R1 may be divalent or trivalent. Moreover, the trivalent R1 may form a bond with X or with W1. In addition, when m=2 in the formula (1), [R1(-W1-R2-W2) b ] m There are two R1s in the formula, and the combination of these two R1s can be a combination of divalent-divalent, divalent-trivalent, trivalent-divalent, and trivalent-trivalent. Moreover, for the trivalent R1, each can form a bond with X or with W1. Similarly, there are modes up to m=10, and for m=1 to 10, each can be (-R1(-X) c ) p A combination of the valence number (divalent or trivalent) of R1 in the formula (A).

[0054] In addition, the largest number of a in formula (1) is [R1(-W1-R2-W2) b ] m In the case where all R1 are trivalent hydrocarbon groups and the R1 is bonded to the left end X as much as possible, wherein X is [R1(-W1-R2-W2) b ] m The number of R1 in: the number obtained by adding 1 quantity to m quantities. Therefore, when m is 10, which is the largest, a is 11, which is the largest. On the other hand, the number of a is the smallest when: (i) [R1 (-W1-R2-W2) b ] m (ii) in [R1(-W1-R2-W2)b]m, R1 contains a trivalent hydrocarbon group, so that the trivalent R1 is as close to [R1(-W1-R2-W2)b]m as possible. b ] m (iii) the case where W1 forms a bond (where m≥1); or (iii) the case where m=0, the minimum value of a is 1.

[0055] In the formula (1), when b=2, it means that the polyamide is [R1(-W1-R2-W2) b ] mR1 in the equation is the base branch, which affects the value of p. The number of p is b = 2 [R1(-W1-R2-W2) b ] m The total number of + 1. That is, the amide bond W2 present in formula (1) and (-R1(-X) c ) p bonding (where m≥1). Therefore, the largest p is when m is the largest 10, in which case b=2 [R1(-W1-R2-W2) b ] m Maximum 10 (10 [R1 (-W1-R2-W2) b ] m All are b = 2), so the maximum value of p is 11. On the other hand, the smallest p is when m = 0, or when m ≥ 1 and all b is b = 1, and b = 2 [R1 (-W1-R2-W2) b ] m is 0, so the minimum value of p is 1.

[0056] In formula (1), c is in (-R1(-X) c ) p In the case where R1 is a divalent hydrocarbon group, it is 1. In the case where (-R1(-X) c ) p In the case where R1 is a trivalent hydrocarbon group, the value is 2.

[0057] The block copolymer (A1) is a polyamide-polyether block copolymer including a polyether block of the Y portion when X is Y equivalent to formula (1) and a polyamide block equivalent to the portion other than Y. In this way, as long as an aqueous composition containing a polyamide block with a specific structure and a block copolymer (A1) with a polyether block and water is used, viscosity can be imparted to water, and even if it is difficult to exert the viscosity imparting effect in the previous composition, sufficient viscosity imparting effect can be exerted. In addition, the allocation during the synthesis of the block copolymer (A1) can also be adjusted, and the structure of the polyamide block and the polyether block is adopted to a specified structure, and the dispersion effect of the pigment in the water-based coating is exerted.

[0058] Here, the viscosity imparting effect in the present invention refers to the effect of increasing the viscosity (thickening) of the water-based paint to which the water-based composition is added. In addition, the dispersion effect in the present invention refers to the effect of uniformly dispersing pigments, carbon nanotubes (CNTs), other fillers, etc. in the water-based paint to which the water-based composition is added. Hereinafter, preferred embodiments of the water-based composition of the present invention are described in detail.

[0059] The block copolymer (A1) is a polyamide-polyether block copolymer obtained by the dehydration reaction of a polyamide and a polyether.

[0060] <Regarding R1>

[0061] R1 in formula (1) is a hydrocarbon group derived from a dicarboxylic acid or tricarboxylic acid when synthesizing the polyamide used as a raw material. That is, R1 is a divalent hydrocarbon group obtained by removing two carboxyl groups from the above-mentioned dicarboxylic acid, or a trivalent hydrocarbon group obtained by removing three carboxyl groups from the above-mentioned tricarboxylic acid. In addition, the carboxyl groups in the dicarboxylic acid and tricarboxylic acid remain as unreacted parts, or are used to form amide bonds or ester bonds during the synthesis of the block copolymer (A1).

[0062] As the above-mentioned dicarboxylic acid, at least one carboxylic acid selected from dicarboxylic acids having 4 to 54 carbon atoms can be used. As such a dicarboxylic acid, for example, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, dimer acid, etc. can be cited. Dimer acid is a polymerized fatty acid obtained by polymerizing (dimerizing) unsaturated fatty acids (for example, unsaturated fatty acids having 18 or 22 carbon atoms) obtained from vegetable oils such as soybean oil, tall oil, linseed oil, and cottonseed oil. Usually, commercially available dimer acids having 36 or 44 carbon atoms and acids obtained by hydrogenating the unsaturated parts of these dimer acids are available. As such commercially available dimer acids, for example, PRIPOL (Japanese: プリポール) 1013, PRIPOL (Japanese: プリポール) 1017, PRIPOL (Japanese: プリポール) 1004 (manufactured by Croda Japan Co., Ltd.), HARIDIMER (Japanese: ハリグイマー) 200, HARIDIMER (Japanese: ハリグイマー) 250, HARIDIMER (Japanese: ハリグイマー) 270S (manufactured by Harima Chemicals Co., Ltd.), Tsunodyme (Japanese: ツノグイム) (registered trademark) 205, Tsunodyme (Japanese: ツノグイム) 228, Tsunodyme (Japanese: ツノグイム) 395 (manufactured by Tsukuno Food Industry Co., Ltd.), etc. can be cited. Some commercially available dimer acids contain monomer acids and trimer acids in addition to dimer acid. For example, HARIDIMER (Japanese: ハリグイマー) 250 contains about 10 to 20% by mass of trimer acid, but there are also high-purity types such as Tsunodyme (Japanese: ツノグイム) 395 that minimize components other than dimer acid. Those containing trimer acid or high-purity types can also be used, but those with a lower content of monomer acid are preferred.

[0063] As the above-mentioned tricarboxylic acid, at least one carboxylic acid selected from tricarboxylic acids having 4 to 54 carbon atoms can be used. As such a tricarboxylic acid, for example, trimer acid, trimellitic acid, etc. can be mentioned. Trimer acid is a polymer fatty acid obtained by distillation refining etc. based on dimer acid to increase the trimer acid content. Usually, trimer acid having 54 carbon atoms is commercially available. As such a commercially available dimer acid, for example, PRIPOL (Japanese: プリポール) 1040 (manufactured by Croda Japan Co., Ltd.), Tsunodyme (Japanese: ツノグイム) (registered trademark) 346 (manufactured by Tsukino Food Industry Co., Ltd.), etc. can be mentioned. In the commercially available trimer acid, in addition to trimer acid, monomer acid and dimer acid are also contained, but those with a smaller content of monomer acid are preferred.

[0064] In addition, within the range that does not hinder the effects of the aqueous composition of the present invention, a monocarboxylic acid can also be used in combination with the above-mentioned dicarboxylic acid and / or tricarboxylic acid. As such a monocarboxylic acid, for example, saturated aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid (docosanoic acid), etc., and unsaturated aliphatic monocarboxylic acids such as oleic acid, linoleic acid, ricinoleic acid, linolenic acid, eicosenoic acid, erucic acid, mixed fatty acids obtained from natural oils (tall oil fatty acid, rice bran fatty acid, soybean oil fatty acid, beef tallow fatty acid, etc.) can be mentioned. In addition, as the monocarboxylic acid, for example, a monocarboxylic acid having a hydroxyl group such as 12-hydroxystearic acid can also be used.

[0065] The above-mentioned dicarboxylic acid and tricarboxylic acid can be used separately alone or in combination of two or more.

[0066] <Regarding R2>

[0067] R2 in formula (1) is a hydrocarbon group derived from a diamine when synthesizing the polyamide which is the raw material of the block copolymer (A1). That is, R2 is a divalent hydrocarbon group obtained by removing two amino groups from the above-mentioned diamine. In addition, the amino groups in the diamine are used to form amide bonds during the synthesis of the block copolymer (A1).

[0068] As the above diamine, at least one amine selected from the group consisting of diamines having 2 to 36 carbon atoms can be used. As such diamines, for example, aliphatic diamines such as ethylenediamine (EDA), propylenediamine (PDA), tetramethylenediamine (TMDA), pentamethylenediamine (PMDA), hexamethylenediamine (HMDA), octamethylenediamine (OMDA), dodecamethylenediamine (DMDA), and trimethylhexamethylenediamine; aromatic diamines such as o-xylenediamine, m-xylenediamine (MXDA), p-xylenediamine (PXDA), and diaminodiphenylmethane; and alicyclic diamines such as isophoronediamine can be mentioned.

[0069] In addition, as the above diamine, a diamine derived from a polymerized fatty acid as a polymerized fatty acid derivative can also be used. As such a polymerized fatty acid derivative, for example, dimer diamine (DDA) as a dimer acid derivative can be exemplified. Dimer diamine, as a dimer acid derivative, is a dimer diamine in which two terminal carboxyl groups of dimer acid are substituted with primary aminomethyl or amino groups, and commercially available dimer diamine can be used. As such commercially available dimer diamine, for example, Priamine (Japanese: プリアミン) 1075, Priamine (Japanese: プリアミン) 1074 (both are manufactured by Croda Japan Co., Ltd.), Versamine (Japanese: バーサミン) 551 (manufactured by BASF Japan Co., Ltd.) and the like can be mentioned.

[0070] In addition, within the range that does not hinder the effects of the aqueous composition of the present invention, a monoamine can be used in combination with the above diamine. As such a monoamine, for example, ethylamine, monoethanolamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, decylamine, laurylamine, myristylamine, cetyl amine, stearyl amine, behenyl amine and the like can be mentioned.

[0071] The above diamines can be used either individually or in combination of two or more.

[0072] <Regarding m>

[0073] As described above, m in the formula (1) is an integer of 0 to 10. When m exceeds 10, the viscosity imparting effect and the dispersion effect required for the present invention cannot be obtained. From the viewpoint of improving the viscosity imparting effect, it is preferable that the amount of m = 0 is small. Specifically, it is preferable that the component with m = 0 in the block copolymer (A1) is 50% by mass or less, more preferably 30% by mass or less, and further preferably 15% by mass or less. The closer the acid / amine ratio is to 1, the smaller the amount of the component with m = 0. In order to investigate the amount of the component with m = 0, first, the mass% of m = 0 is determined by gel permeation chromatography (GPC) of the polyamide before reacting the polyether. Next, as the reactivity of the reaction groups of the component with m = 0 and the component with m ≥ 1 being the same, the mass increase amount when the polyether is reacted is added, and it can be calculated based on the mass of the component with m = 0 and the total mass of A1. For example, using a highly pure type of dimer acid that is easy to analyze (as an example of a commercially available product, Tsunodyme 395 can be cited), in the polyamide reacted with ethylenediamine (EDA), when the acid / amine ratio = 3.8, the component with m = 0 is 50% by mass, when the acid / amine ratio = 2.4, the component with m = 0 is 30% by mass, and when the acid / amine ratio = 1.7, the component with m = 0 is 15% by mass. When using other raw materials, although there are some differences, the amount of m = 0 is also of the same order. Here, the value calculated based on the molecular weight of the polyether and the amount of the reaction groups of each component is the mass% of the component with m = 0. The above description is the result in the case where no component corresponding to m = 0 is added after the polyamide synthesis. In the case where a component corresponding to m = 0 is added, all of these need to be added together and recalculated.

[0074] As described above, X in the formula (1) is independently a carboxyl group or its salt, or Y: R3-(OR4) n -Z-. As the salt of the carboxyl group, for example, there are neutralization salts of the carboxyl group and the following neutralizing bases. As examples of the neutralizing base, there can be cited alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, ammonia as an inorganic amine, alkylamines such as ethylamine and diethylamine, amino alcohols such as 2,2’,2”-nitrilotriethanol, 2,2’-iminodiethanol, 2-(dimethylamino)ethanol, 2-(diethylamino)ethanol, 2-amino-2-methyl-1-propanol, polyetheramines such as JEFFAMIN (registered trademark) M-1000 and JEFFAMIN M-2070 (manufactured by HUNTSMAN) etc.

[0075] The polyether as a raw material when synthesizing the block copolymer (A1) has the formula: R3-(OR4) n -Z T(wherein, R3 is a hydrocarbon group having 1 to 22 carbon atoms, R4 is a divalent hydrocarbon group having 2 to 4 carbon atoms, and Z T is an amino group, a hydroxyl group or a carboxyl group, preferably an amino group or a hydroxyl group. N is an integer of 2 to 100, preferably 2 to 50, more preferably 5 to 50. ) is represented by Z T The above-mentioned polyamide and polyether undergo a dehydration reaction to form Z (ie, an ester bond or an amide bond).

[0076] <About R3>

[0077] The above-mentioned R3 is not particularly limited as long as it is a monovalent aliphatic hydrocarbon group or an aromatic hydrocarbon group having 1 to 22 carbon atoms, and may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, and may be straight-chain, branched, or cyclic.

[0078] As the aliphatic hydrocarbon group, for example, an alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, a cycloalkenyl group, and a cycloalkynyl group can be mentioned. The alkyl group, the alkenyl group, and the alkynyl group can be either straight-chain or branched. In addition, the cycloalkyl group, the cycloalkenyl group, and the cycloalkynyl group can be either monocyclic or polycyclic.

[0079] Examples of the alkyl group include methyl, ethyl, propyl, hexyl, 2-ethylhexyl, dodecyl, tetradecyl, hexadecyl, octadecyl, and behenyl. Examples of the cycloalkyl group include cyclohexyl and norbornyl.

[0080] Examples of the aromatic hydrocarbon group include aryl groups. The aromatic hydrocarbon may be monocyclic or polycyclic. Examples of monocyclic aryl groups include phenyl groups, and examples of polycyclic aryl groups include naphthyl groups.

[0081] R3 may also be a combination of an aliphatic hydrocarbon group and an aromatic hydrocarbon group. Examples of such hydrocarbon groups include arylalkylene groups such as benzyl, alkylarylene groups such as tolyl, dialkylarylene groups such as xylyl, etc. In addition, R3 may also be a combination of two or more aromatic hydrocarbon groups. Examples of such hydrocarbon groups include arylarylene groups such as biphenyl, arylalkylarylene groups such as styrenated phenyls, etc.

[0082] <About R4>

[0083] R4 is not particularly limited as long as it is a divalent aliphatic hydrocarbon group having 2 to 4 carbon atoms, and may be either a saturated hydrocarbon group or an unsaturated hydrocarbon group, and may be either a straight chain, a branched chain, or a cyclic group, but saturated straight chain hydrocarbon groups and saturated branched chain hydrocarbon groups are particularly preferred. In addition, preferably the number of carbon atoms is 2 to 3, and more preferably the number of carbon atoms is 2. In addition, it may also contain different numbers of carbon atoms or different shapes. In the case of containing different numbers of carbon atoms, it is preferred to contain 2 to 3 carbon atoms, and more preferably to contain 2 carbon atoms. Further, in the case of containing different numbers of carbon atoms, it is preferred to contain more than 50 mol% of the component with a carbon number of 2, and more preferably to contain more than 75 mol%. In addition, as a raw material for the synthesis of the block copolymer (A1), by using a polyether with a carbon number of 2 of R4 of more than 50 mol% of the total raw material polyether, it is possible to "contain more than 50 mol% of the component with a carbon number of 2".

[0084] As the aliphatic hydrocarbon group, for example, alkylene, alkenylene, alkynylene, cycloalkylene, cycloalkenylene, etc. can be cited. Alkylene, alkenylene, and alkynylene can be either straight chain or branched. As examples of alkylene, there are ethylene, propylene, etc.

[0085] <Preferred structural example of block copolymer (A1)>

[0086] In the aqueous composition of the present invention, X as Y in all X in the block copolymer (A1) represented by the formula (1) is 5 mol% or more. When the amount is less than 5 mol%, the viscosity imparting effect and the dispersion effect required in the present invention cannot be exerted. The mol% of the Y portion can be controlled by adjusting the polyamide / polyether ratio when synthesizing the block copolymer (A1), but the reaction yield must be considered when the reaction yield is not 100%. In addition, it is also possible to 1 H-NMR was used for analysis.

[0087] From the viewpoint of improving the viscosity imparting effect, the aqueous composition of the present invention preferably contains a block copolymer (A1) in which at least a portion of X in formula (1) is a carboxyl group or a salt thereof. In this case, X as a carboxyl group or a salt thereof is preferably 30 mol% or more, more preferably 40 mol% or more, and further preferably 50 mol% or more relative to the total amount of X in the block copolymer (A1) contained in the aqueous composition. The amount of X as a carboxyl group or a salt thereof can be controlled by adjusting the polyamide / polyether ratio when synthesizing the block copolymer (A1), but the reaction yield needs to be taken into consideration when the reaction yield is not 100%. Alternatively, 1 Analyzed by H-NMR.

[0088] From another point of view for improving the viscosity imparting effect, the remaining mass after removing the Y portion from all the block copolymers (A1) contained in the aqueous composition is preferably 0% by mass or more and 90% by mass or less relative to the mass of the entire block copolymer (A1). The remaining mass after removing the Y portion from the block copolymer (A1) can be controlled by adjusting the amount of polyamide added / the amount of polyether added when synthesizing the block copolymer (A1), but the reaction yield needs to be considered when the reaction yield is not 100%. It can also be controlled by using an internal standard 1 Analyzed by H-NMR.

[0089] From the further other viewpoints for improving the viscosity imparting effect, the acid value of the block copolymer (A1) is preferably 15 to 80, more preferably 15 to 60, and more preferably 15 to 50. When the acid value of the block copolymer (A1) is less than 15, the acid-base interaction of the block copolymer (A1) is too little, and there is a situation where the thickening effect is reduced. When the acid value exceeds 80, the molecular weight of the block copolymer (A1) is too small and the thickening effect is reduced. In addition, the high acid value of the block copolymer (A1) means that the polyamide part is a low molecular weight and the amount of the polyether part is small.

[0090] Here, the acid value in this specification can be measured according to JIS K0070-1992. In addition, the acid value refers to the mg number of potassium hydroxide required to neutralize the free fatty acids contained in 1g of the sample. In addition, there are neutralization titration and potentiometric titration methods for determining the acid value, but the acid value in this specification is the value measured by the neutralization titration. In addition, the reaction yield can be obtained by using the acid value measured by this method, and the acid value of the polyamide / polyether mixture before the reaction is taken as the reaction yield 0%, and the value of the theoretical acid value is taken as the reaction yield 100%.

[0091] From another viewpoint of improving the viscosity imparting effect, 50 mol % or more of either or both of R1 and R2 in formula (1) is preferably a divalent hydrocarbon group having 34 or more carbon atoms.

[0092] From another viewpoint for improving the viscosity imparting effect, it is preferred that at least a part of X in formula (1) is Y and R4 has 2 carbon atoms (OR4) n The mass of the (OR4)n site is 5% by mass or more and 45% by mass or less relative to the mass of the entire block copolymer (A1). The mass of the (OR4)n site is calculated based on the carbon number of R4 in the added polyether raw material being 2. n The mass of the polyamide is calculated by subtracting the amount of dehydration from the total amount of the polyamide and the polyether, and the total mass is calculated by subtracting the amount of dehydration from the total amount of the polyamide and the polyether, and the carbon number of R4 is 2 (OR4)n The mass of the product is divided by the total mass and converted into a percentage value as above (OR4) n Furthermore, in the case where unreacted raw materials are present, the unreacted amount is calculated based on the reaction yield, and it is necessary to calculate the amount of (OR4) calculated as described above. n The unreacted amount can also be removed by using an internal standard 1 Analyzed by H-NMR.

[0093] From another viewpoint of improving the viscosity imparting effect, it is preferred to further contain a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), wherein at least a part of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5 mass% or more and 50 mass% or less based on the total mass of the block copolymer (A1) and the polyether (B1).

[0094] R5-(OR6) q -OR7…(2)

[0095] In the above formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms. R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms. R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. q is an integer of 2 to 100.

[0096] In the block copolymer (A1), R4 has 2 carbon atoms (OR4) n The carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites can be calculated by calculating the total mass of the sites according to the number of carbon atoms of R4 in the block copolymer (A1) being 2 (OR4) n The mass and addition amount of, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The mass of the block copolymer (A1) and the amount of the polyether (B1) added are respectively calculated to obtain the total mass, and the total mass is divided by the total mass of the block copolymer (A1) and the amount of the polyether (B1) added to calculate the above (OR4). n Location and (OR6) q The ratio of the total mass of the parts (mass %) can also be calculated by using an internal standard 1 Analyzed by H-NMR.

[0097] The case where R7 of the polyether (B1) is H is an example of a polyether used as a raw material when synthesizing the block copolymer (A1). R5 and R6 are the same as the above-mentioned R3 and R4, respectively. q is the same as the above-mentioned n.

[0098] In the case where R7 is a hydrocarbon group having 1 to 4 carbon atoms, there is no particular limitation as long as R7 is a monovalent aliphatic hydrocarbon group having 1 to 4 carbon atoms, and it may be either a saturated hydrocarbon group or an unsaturated hydrocarbon group, and may be either a straight chain, a branched chain, or a cyclic chain. Examples of aliphatic hydrocarbon groups include alkyl, alkenyl, alkynyl, cycloalkyl, and cycloalkenyl groups. Alkyl and alkenyl groups may be either straight chain or branched chain. Examples of alkyl groups include methyl, ethyl, and propyl groups. Examples of cycloalkyl groups include cyclopropyl and the like.

[0099] From another viewpoint of improving the viscosity imparting effect, it is preferred that the block copolymer (A1) further contains the above-mentioned polyether (B1), at least a part of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5% by mass or more and 50% by mass or less relative to the total mass of the non-volatile content in the aqueous composition. In the block copolymer (A1), R4 has 2 carbon atoms (OR4) n The carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites can be calculated by calculating the total mass of the sites according to the number of carbon atoms of R4 in the block copolymer (A1) being 2 (OR4) n The mass and addition amount of, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The mass and addition amount are calculated separately (OR4) n Location and (OR6) q The above (OR4) is calculated by dividing the total mass of the added block copolymer (A1) and the polyether (B1) by the total mass of the added block copolymer (A1) and the polyether (B1) and the amount of other non-volatile materials added arbitrarily. n Location and (OR6) q In addition, when the above (OR4) is identified by analysis, n Location and (OR6) q In the case of the total mass of the parts, it can be calculated as follows. After drying the solution containing the synthesized block copolymer (A1) and removing the volatile components, the total mass of the parts can be calculated by using an internal standard. 1 H-NMR can determine that the number of carbon atoms in R4 is 2 (OR4) n The carbon number of the site and R6 is 2 (OR6) qThe ratio of the total mass of the parts (mass %). In addition, any internal standard can be used as long as the peak of the quantitative object is separated from the reference peak of the internal standard and dissolved in the measurement medium. As an example, dimethyl terephthalate can be mentioned.

[0100] From another perspective for improving the viscosity imparting effect, a hydrophobic solid (crystallized product) may be further added to the block copolymer (A1) represented by formula (1). The hydrophobic solid is insoluble in water, and any type of solid may be used as long as it is solid at room temperature. For example, polyethylene waxes such as amide wax, hydrogenated castor oil, polyethylene, and oxidized polyethylene may be cited.

[0101] In addition, from the viewpoint of improving the dispersion effect, a block copolymer (A1) containing all X in the formula (1) as Y is preferred. In this case, it is preferred that 80 mol% or more of all X in the formula (1) as Y. The amount of X as Y (mol%) is equal to the reaction yield when the reactive group ratio of polyether / polyamide is 1 or more when synthesizing the block copolymer (A1). When the reactive group ratio of polyether / polyamide is less than 1, it can be calculated by multiplying the ratio by the reaction yield. Alternatively, it can be calculated by 1 Analyzed by H-NMR.

[0102] From another viewpoint of improving the dispersing effect, the acid value of the mixture of the block copolymer (A1) and the polyether (B1) further containing the above-mentioned polyether (B1) is preferably 10 or less. The lower the acid value of the mixture, the more the dispersing effect of the pigment, etc. based on the aqueous composition of the present invention can be improved. In addition, the method for measuring the acid value is as described above.

[0103] From another viewpoint for improving the dispersing effect, the number of carbon atoms of R3 in the formula (1) is preferably 1 to 4, and more preferably 1.

[0104] From another viewpoint for improving the dispersion effect, the block copolymer (A1) in which m=0 in the formula (1) is preferably 50% by mass or less based on the mass of the entire block copolymer (A1) contained in the aqueous composition.

[0105] From another viewpoint of improving the dispersing effect, it is preferred that the block copolymer (A1) further contains the above-mentioned polyether (B1), at least a part of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) qThe total mass of the sites is 50 mass% or more and 90 mass% or less based on the total mass of the block copolymer (A1) and the polyether (B1).

[0106] From another viewpoint of improving the dispersing effect, it is preferred that the block copolymer (A1) further contains the above-mentioned polyether (B1), at least a part of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 50 mass % or more and 90 mass % or less with respect to the total mass of the nonvolatile content in the aqueous composition.

[0107] (water)

[0108] The aqueous composition of the present invention is for water-based coatings and is obtained by dispersing the block copolymer (A1) as an active ingredient in a medium mainly composed of water. As water, for example, deionized water (ion exchange water) can be used. In the aqueous composition of the present invention, viscosity can be imparted to water by making the mass ratio of the block copolymer (A1) relative to water within a specific range.

[0109] (Mass ratio of block copolymer (A1) to water)

[0110] In the aqueous composition of the present invention, A1 / water, which is the mass ratio of the block copolymer (A1) to water, is set to 5 / 95 to 50 / 50. When A1 / water is less than 5 / 95, the viscosity imparting effect and the dispersion effect required by the present invention cannot be exerted, or there are few active ingredients, so it is not economical. When A1 / water exceeds 50 / 50, the amount of the block copolymer (A1) relative to water is too much, so the block copolymer (A1) in the aqueous composition cannot be fully dispersed, and the viscosity imparting effect and the dispersion effect required by the present invention cannot be exerted. From the viewpoint of further improving the viscosity imparting effect and the dispersion effect, the lower limit of A1 / water is preferably more than 10 / 90. On the other hand, the upper limit of A1 / water is preferably less than 40 / 60, more preferably less than 35 / 65, and further preferably less than 30 / 70.

[0111] (Other ingredients)

[0112] The aqueous composition of the present invention may also contain auxiliary agents (other ingredients) for the purpose of imparting other functions. For example, various auxiliary agents may be added for the purpose of maintaining the gloss of the coating film, improving the dispersibility of the pigment, the defoaming property of the aqueous coating composition, the flow surface, etc. As representative auxiliary agents in the aqueous composition of the present invention, for example, the following neutralization bases, solvents, surfactants, etc. may be cited.

[0113] <Alkali for neutralization>

[0114] For example, the aqueous composition of the present invention may contain a neutralizing base such as an amine in order to disperse the block copolymer (A1) in a medium mainly composed of water (i.e., as a hydrophilizing aid that helps hydrophilize the block copolymer (A1)). The content of the neutralizing base is preferably 150 mol% or less, more preferably 110 mol% or less, relative to the total amount of the acid in the aqueous composition.

[0115] As such a neutralization base, both organic bases and inorganic bases can be used. As an organic base, for example, alkylamines such as ethylamine, diethylamine, and triethylamine, and ethanolamine, diethanolamine (also known as 2,2'-iminodiethanol), triethanolamine (also known as 2,2', 2"-nitrilotriethanol), N,N-dimethylethanolamine (also known as 2-(dimethylamino)ethanol.), 2-(diethylamino)ethanol, 2-amino-2-methyl-1-propanol and other alcoholamines, JEFFAMIN (Japanese: Bu Ef Amin) (registered trademark) M-1000, JEFFAMIN (Japanese: Bu Ef Amin) M-2070 (the above are manufactured by HUNTSMAN) and other polyetheramines can be used. As an inorganic base, for example, sodium hydroxide, potassium hydroxide, ammonia, etc. can be used. These can be used alone or in combination of two or more.

[0116] <Solvent>

[0117] The aqueous composition of the present invention makes it easy to disperse the block copolymer (A1) in a medium with water as the main body, so it can also contain solvents other than water. As the first solvent (C), there is no particular restriction, but a solvent having at least one substituent selected from the group consisting of a hydroxyl group, an ether group, an ester group, an amide group and a ketone group can also be used. As examples of the solvent, alcohol solvents, glycol ether solvents, diglycol ether (diglycol ether; diglycol ether) solvents, triglycol ether (triglycol ether; triglycol ether) solvents, ester solvents and amide solvents can be cited. However, the first solvent (C) does not contain a solvent equivalent to the polyether (B1) as a diglycol solvent and a triglycol solvent. As an alcohol solvent, there is a monohydric alcohol, for example, aliphatic alcohols such as methanol, ethanol, propanol, butanol, isobutanol, isopropanol, pentanol, hexanol, heptanol, octanol, 2-ethylhexanol, and cyclic alcohols such as benzyl alcohol can be cited. As the glycol ether solvent, for example, ethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether (also called 2-butoxyethanol), ethylene glycol monoisobutyl ether, ethylene glycol monohexyl ether, 2-ethylhexanediol, propylene glycol monomethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, phenoxyethanol (phenyl glycol), ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, etc. can be mentioned. As the diethylene glycol ether solvent, for example, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monomethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, etc. can be mentioned. As the triethylene glycol ether solvent, for example, triethylene glycol dimethyl ether, etc. can be mentioned. As ester solvents, for example, dibasic esters such as methyl glutarate, methyl succinate, methyl adipate, ethyl acetate, butyl acetate, hexyl acetate, heptyl acetate, propylene glycol monomethyl ether acetate, amyl propionate, ethyl ethoxypropionate, and trimethylpentanediol monoisobutyrate (also known as Texanol) can be cited. As amide solvents, for example, non-cyclic amides such as dimethylformamide, diethylformamide, dimethylacetamide, 3-methoxy-N, N-dimethylpropionamide, hexamethylphosphoramide, and cyclic amides such as N-methylpyrrolidone can be cited. In addition, polyols such as ethylene glycol, propylene glycol, butanediol, glycerol, sorbitol, and xylitol can also be used as solvents. Solvents such as those cited above can be used alone or in combination of two or more.

[0118] <Surfactant>

[0119] The aqueous composition of the present invention may contain a surfactant as an optional component. The surfactant is used as a hydrophilizing aid to hydrophilize the block copolymer (A1) and facilitate the dispersion of the block copolymer (A1) in a medium mainly composed of water. As an example of such a surfactant, the above-mentioned polyether (B1) may also be used. In addition to the polyether (B1), polyoxyethylene hydrogenated castor oil, polyoxyethylene castor oil, polyoxyethylene carboxylic acid esters such as polyoxyethylene stearate, polyoxyethylene laurate, and polyoxyethylene oleate, polyoxyethylene hydrogenated castor oil monoisostearate, polyoxyethylene triisostearate, and polyoxyethylene glycerol fatty acid esters such as polyoxyethylene glycerol monoisostearate, polyoxyethylene sorbitan aliphatic esters such as polyoxyethylene sorbitan monostearate, and polyoxyethylene oxypropylene copolymers, other nonionic surfactants, anionic surfactants such as sodium laurate, ammonium laurate, sodium stearate, ammonium stearate, sodium lauryl sulfate, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium polyoxyethylene lauryl ether acetate, and polyoxyethylene alkyl ether potassium phosphate, and polymer surfactants can be used.

[0120] (Other effects)

[0121] In addition, the aqueous composition of the present invention can control the orientation of the flaky pigment when applying by improving the viscosity of the coating, and this effect can be used to improve the improvement of the angular flop of the metallic coating and the appearance of the coating. For example, it has a low viscosity at a high shear rate such as during coating, and a high viscosity at a low shear rate such as after coating, which is conducive to obtaining a coating showing high angular flop. Therefore, as the aqueous composition of the present invention, a coating showing high angular flop can be provided by using a material showing such viscosity.

[0122] (About combined use with other viscosity modifiers)

[0123] The diluted composition and water-based coating composition using the aqueous composition of the present invention can be used in combination with other viscosity modifiers. By using other viscosity modifiers in combination, it is possible to have a viscosity different from the aqueous composition of the present invention. For example, by using a viscosity modifier that thickens at a high shear rate, it is possible to thicken at both a high shear rate and a low shear rate. As a viscosity modifier that can thicken at such a high shear rate, there are viscosity modifiers using carbamate viscosity modifiers, acrylic acid viscosity modifiers, cellulose modified material viscosity modifiers, polysaccharide viscosity modifiers, etc. In addition, as other viscosity modifiers that can be used in combination, amide viscosity modifiers, polyamide viscosity modifiers, urea viscosity modifiers, cellulose nanofibers (CNF), inorganic viscosity modifiers, etc. can be cited.

[0124] There are no particular restrictions on the urethane-based viscosity modifiers, but examples include ADEKA NOL (Japanese: アデ力ノ一ル) (registered trademark) UH-752, ADEKA NOL (Japanese: アデ力ノ一ル) UH-540, ADEKA NOL (Japanese: アデ力ノ一ル) UH-420 (manufactured by ADEKA CORPORATION), ACRYSOL RM-2020NPR, RM-8W, RM-12W (manufactured by DOW CHEMICAL COMPANY), SN THICKENER (Japanese: シツクナ一) 612, SN THICKENER (Japanese: シツクナ一) 621N (manufactured by San Nopco Limited), RHEOLATE (registered trademark) 244, RHEOLATE 278 (manufactured by Elementis Japan), TAFIGEL (registered trademark) PUR-45, TAFIGEL PUR-61 (manufactured by MUNZING), etc. There are no particular restrictions on the acrylic-based viscosity modifiers, but examples include DISPARLON (Japanese: デイスパ口ン) (registered trademark) AQ-001, DISPARLON (Japanese: デイスパ口ン) AQ-002, DISPARLON (Japanese: デイスパ口ン) AQ-021 (manufactured by Kusumoto Chemicals, Ltd.), RHEOVIS (registered trademark) AS1130 (manufactured by BASF Societas Europeae), ACRYSOL ASE-60, ACRYSOL TT-615 (manufactured by DOW CHEMICAL COMPANY), SN THICKENER (Japanese: シツクナ一) 617, SN THICKENER (Japanese: シツクナ一) 630, SN THICKENER (Japanese: シツクナ一) 640 (manufactured by San Nopco Limited), THIXOL (Japanese: チクゾ一ル) (registered trademark) K-1000 (manufactured by Kyoeisha Chemical Co., Ltd.), etc. There are no particular restrictions on the cellulose-based modified viscosity modifiers, but examples include carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, ethyl cellulose, etc. As commercially available products, examples include HEC Daicel (Japanese: グイ七ル) (registered trademark) SP600N (manufactured by Daicel Corporation), CELLOSIZE (Japanese: 七口サイズ) QP-4400-H, CELLOSIZE (Japanese: 七口サイズ) QP-52000-H (manufactured by DOW CHEMICAL COMPANY), etc. There are no particular restrictions on the polysaccharide-based viscosity modifiers, but examples also include xanthan gum, carrageenan, guar gum, etc. There are no particular restrictions on the amide-based viscosity modifiers, but those described in International Publication No. 2022 / 097747 can be used, etc.The polyamide viscosity modifier is not particularly limited, but examples thereof include DISPARLON AQ-600, DISPARLON AQ-630, DISPARLON AQ-633E, DISPARLON AQH-800, DISPARLON AQH-810 (all manufactured by Kusumoto Chemicals Co., Ltd.), THIXOL W-310P, THIXOL W-400LP (all manufactured by Kyoeisha Chemical Co., Ltd.), ASA TW-121, AS-ATW-124 (all manufactured by Ito Oil Chemicals Co., Ltd.), RHEOBYK (registered trademark) -440 (manufactured by Byk-Chemie), etc. The urea-based viscosity modifier is not particularly limited, but RHEOBYK-420 (manufactured by Byk-Chemie) etc. are mentioned. CNF is not particularly limited, but TEMPO-oxidized CNF, carboxymethylated CNF, phosphated CNF, sulfated CNF, mechanically defibrated CNF, bacterial CNF etc. are mentioned. The inorganic viscosity modifier is not particularly limited and may be a natural mineral or a synthetic material. For example, silicate clay minerals such as sepiolite, bentonite, and hectorite may be cited. Commercially available products include PANGEL (registered trademark) AD (manufactured by Tolsa SA), LAPONITE (registered trademark) RD, LAPONITE RDS (manufactured by Byk-Chemie), BENTONE (registered trademark) EW (manufactured by Elementis Japan), etc. When these are used in combination with the dilution composition and the water-based coating composition using the aqueous composition of the present invention, one may be used alone or two or more may be used in combination.

[0125] (Method for producing aqueous composition)

[0126] First, prepare a polyamide and a polyether as raw materials for synthesizing a block copolymer (A1). Next, the prepared polyamide and the polyether can be subjected to a dehydration reaction to obtain a block copolymer (A1). Further, the block copolymer (A1) is dispersed in water to obtain an aqueous composition of the present invention. When the block copolymer (A1) is dispersed in water, the above-mentioned neutralization alkali or solvent can also be added as needed.

[0127] <Synthesis of Polyamide>

[0128] The polyamide used in the synthesis of the block copolymer (A1) of the present invention can be synthesized by subjecting the above-mentioned diamine (which may also contain a monoamine. Hereinafter, referred to as the "amine component") to a polycondensation reaction with a dicarboxylic acid and / or a tricarboxylic acid (which may also contain a monocarboxylic acid. Hereinafter, referred to as the "carboxylic acid component") under known reaction conditions. For example, the amine component and the carboxylic acid component as raw materials are added to a reaction container such as a four-necked flask, and the raw materials are stirred under an inert gas atmosphere (for example, under a nitrogen gas flow, etc.) to obtain a mixture. Thereafter, the mixture of the raw materials is heated and subjected to a polycondensation reaction at 150°C to 200°C for 2 to 10 hours to synthesize the polyamide.

[0129] In this case, the molar ratio of the amine component to the carboxylic acid component (mol% of the amine component / mol% of the carboxylic acid component) is preferably less than 1. That is, it is preferred that the carboxylic acid component in excess relative to the amine component is subjected to polycondensation. In this case, at least one terminal of the polyamide (corresponding to X in formula (1)) is a carboxyl group. However, at least one terminal of the polyamide is not necessarily a carboxyl group, and all terminals may be amino groups.

[0130] <Preparation of polyether>

[0131] The polyethers used for the synthesis of the block copolymer (A1) of the present invention can be synthesized by methods known to those skilled in the art. For example, they can be synthesized by the method described in Japanese Patent Laid-Open No. 2002-212125. As an example, an alkyl monohydric alcohol as a raw material and potassium hydroxide are added to a stainless steel autoclave equipped with stirring and temperature control functions. After replacing the nitrogen, the temperature is raised to 120 °C while stirring. Next, the temperature is maintained at 120 ± 5 °C and the pressure is maintained at about 3 atm, and ethylene oxide is pressured in and reacted for 20 minutes. An alkyl polyether monohydric alcohol can be obtained by aging it at this temperature for 2 hours and 30 minutes and then cooling it to 40 °C. In addition, as the polyether used for the synthesis of the block copolymer (A1), commercially available products can also be used. As such commercially available products, for example, blaunon (Japanese: ブラウノン) (registered trademark) SR-715, blaunon (Japanese: ブラウノン) SR-720, blaunon (Japanese: ブラウノン) BE-10, blaunon (Japanese: ブラウノン) BE-20, blaunon (Japanese: ブラウノン) BE-30, blaunon (Japanese: ブラウノン) DSP-12.5, blaunon (Japanese: ブラウノン) PH-5, blaunon (Japanese: ブラウノン) SRP-0430B, FINESURF (Japanese: フアインサ一フ) (registered trademark) 230, FINESURF (Japanese: フアインサ一フ) 320, FINESURF (Japanese: フアインサ一フ) 400, FINESURF (Japanese: フアインサ一フ) FO-160, FINESURF (Japanese: フアインサ一フ) 7045 (manufactured by Aoki Yushi Industry Co., Ltd. above), JEFFAMIN (Japanese: ジエファ一ミン) (registered trademark) M-1000, JEFFAMIN (Japanese: ジエフマ一ミン) M-2070 (manufactured by HUNTSMAN above), UNIOX (Japanese: ュニオツクス) (registered trademark) M-400, UNIOX (Japanese: ュニオツクス) M-550, UNIOX (Japanese: ユニオツクス) M-1000, UNIOX (Japanese: ュニオツクス) M-2000, UNIOX (Japanese: ユニオツクス) M-4000 (manufactured by NOF Corporation above), Newcol (Japanese: ニュ一コ一ル) (registered trademark) 2310, Newcol (Japanese: ニュ一コ一ル) 2320, Newcol (Japanese: ニユ一コ一ル) NT-12, Newcol (Japanese: ニュ一コ一ル) NT-15, Newcol (Japanese: ニュ一コ一ル) NT-20, Newcol (Japanese: ニュ一コ一ル) NT-30, Newcol (Japanese: ニユ一コ一ル) 1004,Newcol (Japanese: ニユ一コ一ル) 1006, Newcol (Japanese: ニュ一コ一ル) 1008, Newcol (Japanese: ニユ一コ一ル) 1820, Newcol (Japanese: ニユ一コ一ル) 710, Newcol (Japanese: ニユ一ユ一ル) 719, Newcol (Japanese: ニユ一コ一ル) 729 (manufactured by Nippon Emulsifier Co., Ltd. as above), EMULGEN (Japanese: エマルゲン) (registered trademark) 106, EMULGEN (Japanese: エマルゲン) 220, EMULGEN (Japanese: エマルゲン) 350, EMULGEN (Japanese: エマルゲン) 408, EMULGEN (Japanese: エマルゲン) 709, EMULGEN (Japanese: エマルゲン) 2025G, EMULGEN (Japanese: エマルゲン) A-90, EMULGEN (Japanese: エマルゲン) A-500 (manufactured by Kao Corporation as above), NOIGEN (Japanese: ノイゲン) (registered trademark) TDS-100, NOIGEN (Japanese: ノイゲン) TDX-120D, NOIGEN (Japanese: / イゲン) EA-137, NOIGEN (Japanese: ノイゲン) SD-70 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd. as above), EMALEX (Japanese: エマレツクス) (registered trademark) BHA-5, EMALEX (Japanese: エマレツクス) BHA-20, EMALEX (Japanese: エマレツクス) DAPE-0212, EMALEX (Japanese: エマレツクス) 1615, EMALEX (Japanese: エマレツクス) 1820, EMALEX (Japanese: エマレツクス) OD-16 (manufactured by Nippon Emulsion Co., Ltd. as above), etc.

[0132] <Synthesis of block copolymer (A1)>

[0133] By subjecting the polyamide and polyether obtained as described above to a dehydration reaction, block copolymer (A1) is obtained. As the reaction vessel, for example, the same vessel as used for the synthesis of the above polyamide can be used. The mol ratio of polyamide to polyether is preferably 0.10 to 1.50 mol relative to 1.00 mol of polyamide, and more preferably 0.20 to 1.00 mol relative to 1.00 mol of polyamide. In addition, the dehydration reaction can be carried out, for example, at 200 to 250 °C for 3 to 5 hours. Further, in the case where block copolymer (A1) is liable to be colored, for example, 0.1 to 1.0 parts by mass of a small amount of hypophosphorous acid or the like can be added relative to 100 parts by mass in total of polyamide and polyether to suppress coloring.

[0134] As described above, the block copolymer (A1) can be obtained by mixing an amine component and a carboxylic acid component as raw materials of polyamide and a polyether and performing a dehydration reaction, instead of synthesizing polyamide in advance and then performing a dehydration reaction on polyamide and polyether.

[0135] <Dispersion of Block Copolymer (A1)>

[0136] The block copolymer (A1) can be dispersed in water by a known polymer dispersion method. For example, deionized water is added to a container such as a four-necked flask and heated to 60 to 75°C. On the other hand, the block copolymer (A1) is mixed with a neutralizing alkali and a solvent to prepare a liquid mixture. While stirring the liquid mixture, it is gradually added to the heated deionized water in the container. After adding the liquid mixture, stirring is further continued for about 5 to 120 minutes in the range of 50 to 80°C to obtain a dispersion. After the stirring is completed, the dispersion is transferred to another container and left to stand at room temperature for about 12 to 72 hours to obtain an aqueous composition of the present invention.

[0137] (Use of aqueous composition)

[0138] The use of the aqueous composition of the present invention is not particularly limited as long as it contains water. However, the aqueous composition of the present invention can be preferably used for water-based metallic paints using pearl pigments such as aluminum pigments and mica, or water-based anticorrosive paints using pigments with large particles and large specific gravity such as anticorrosive pigments. In addition, the aqueous composition of the present invention can also be preferably used for water-based clear paints, water-based paints using common coloring pigments and extender pigments other than the above, and water-based coating materials such as water-based inks.

[0139] [Dilution composition]

[0140] The dilution composition of the present invention is a composition obtained by diluting the above-mentioned aqueous composition. In the dilution composition, A1 / water, which is the mass ratio of the block copolymer (A1) to water, is 0.01 / 99.99 to 5 / 95, preferably 0.05 / 99.95 to 5 / 95, more preferably 0.1 / 99.9 to 5 / 95, and further preferably 0.2 / 99.8 to 5 / 95. When A1 / water is less than 0.01 / 99.99, the viscosity imparting effect and the dispersing effect when the aqueous composition is diluted are lost. As a medium for diluting the aqueous composition, for example, water, resin liquid (emulsion resin liquid, dispersed resin liquid, etc.), coating, ink, pigment slurry obtained by dispersing pigments, etc. in a specified medium, etc. can be cited.

[0141] The diluted composition can be obtained by directly diluting the aqueous composition with the above-mentioned medium. Alternatively, the diluted composition can be obtained by preparing a masterbatch of the aqueous composition diluted with a predetermined medium (water, etc.) and diluting the masterbatch with the above-mentioned medium.

[0142] [Water-based coating composition]

[0143] The water-based coating composition of a preferred embodiment of the present invention contains the above-mentioned water-based composition and glossy pigment. In addition, the water-based coating composition of the present invention may further contain other additives such as water-based resin, pigment other than glossy pigment, defoamer, film-forming aid, pH adjuster, etc. in addition to the water-based composition and glossy pigment.

[0144] (Content of aqueous composition)

[0145] The aqueous composition of the present invention is different according to the type of aqueous resin as a binder (binder) in the aqueous coating composition, the deployment composition of the pigment, etc., but usually, the content of the block copolymer (A1) contains an amount of 0.01% by mass or more and 5% by mass or less relative to the total solid content of the aqueous coating composition, preferably an amount of 0.05% by mass or more and 2% by mass or less, more preferably an amount of 0.1% by mass or more and 1% by mass or less, and further preferably an amount of 0.2% by mass or more and 0.5% by mass or less. By making the content of the aqueous composition within the above range, the addition effect of the aqueous composition (the viscosity imparting effect and the dispersion effect to the aqueous coating composition) can be further improved.

[0146] (Water-based resin)

[0147] The water-based resin contained in the water-based coating composition of the present invention as a bonding agent is a resin component dispersed in a medium with water as the main body. As a resin component, for example, acrylic resin, acrylic silicone resin, alkyd resin, polyester resin, urethane resin, epoxy resin, silicone resin, fluororesin, etc. can be cited. As the form of water-based resin, it is divided into water-soluble, (colloid) dispersion liquid, and emulsion according to the dispersion form, but no matter what form can be applicable. These resins can be, for example, heat-cured, ultraviolet-cured, electron-beam-cured, oxidative-cured, photocation-cured, peroxide-cured, and resins cured with chemical reactions in the presence or absence of catalysts, or resins with high glass transition points and not accompanied by chemical reactions and only by volatilizing the diluent medium to become coatings. In addition, as a curing agent, for example, amino resins, melamine resins, isocyanate compounds, blocked isocyanate compounds, and epoxy compounds, etc. can be cited.

[0148] (Glossy Pigment)

[0149] The glossy pigment used in the present invention is not limited to any type as long as it can impart a metallic luster and gloss to the coating film. For example, aluminum, aluminum oxide, nickel, zinc, iron, stainless steel, bismuth, other metallic pigments, pearl pigments such as mica, aluminum flake powder, copper flake powder, mica-like iron oxide, mica, and metallic pigments such as flaky powders of mica coated with metal oxides, glass flakes, graphite, etc. can be used.

[0150] (Other pigments)

[0151] As other pigments other than the glossy pigment, body pigments and coloring pigments commonly used in water-based coatings can be cited. As body pigments, for example, there are calcium carbonate (heavy calcium carbonate (GCC), precipitated calcium carbonate (PCC), etc.), barium sulfate, silicon dioxide, aluminum hydroxide, talcum powder, organic fiber, glass powder, etc. In addition, as coloring pigments, for example, there are titanium dioxide, carbon black, chrome yellow, cadmium yellow, ochre, titanium yellow, zinc chromate, red iron oxide, aluminosilicate, quinacridone series, phthalocyanine series, anthraquinone series, pyrrolopyrrole diketo series, benzimidazolone series and isoindolinone series, etc.

[0152] (Other additives)

[0153] The water-based coating composition of the present invention may contain other substances, for example, dehydrating agents (for example, silane coupling agents), adhesion promoters, surfactants, curing catalysts, film-forming aids, desiccants, antifouling agents, sensitizers, antioxidants, light stabilizers, ultraviolet absorbers, water-resistant agents, preservatives and mildew preventers, defoaming agents, leveling agents, dispersants, flame retardants, antistatic agents, stripping agents, deodorants, pH adjusters, fragrances and other additives, within the scope of not impairing its characteristics and the purpose of the present invention.

[0154] (Method for producing water-based coating composition)

[0155] The water-based coating composition of the present invention can be manufactured according to a known method for manufacturing water-based coatings. For example, after stirring and mixing the above-mentioned water-based composition and components other than the pigment in a medium mainly composed of deionized water (ion exchange water) or the like, pH adjustment is performed as required to prepare a clear coating. The water-based composition and the pigment are added to the clear coating to be dispersed in the clear coating, thereby being able to manufacture the water-based coating composition.

[0156] In addition, as the opportunity of adding the water-based composition of the present invention to the water-based coating composition, it can be the process of mixing the pigment as described above, or it can be added after manufacturing the water-based coating, or it can be added as a masterbatch. In addition, the equipment used for the dispersion of the water-based composition and the pigment can use the equipment commonly used in the manufacture of water-based coatings. Further, the stirring speed and the stirring time conditions during the dispersion of the water-based composition and the pigment are not particularly limited, and can be appropriately set while confirming the dispersion state of the water-based composition and the pigment.

[0157] (Application of water-based coating composition)

[0158] The water-based paint composition of the present invention can be preferably used as a water-based metal paint and a water-based anti-corrosion paint using aluminum pigments, pearl pigments such as mica, or pigments with large particles and large specific gravity such as anti-corrosion pigments. In addition, the water-based paint composition of the present invention can be preferably used as a water-based paint using common coloring pigments and extender pigments other than the above, and a water-based coating material such as water-based ink.

[0159] The preferred embodiments of the present invention are described above, but the present invention is not limited to the above-mentioned embodiments. That is, other embodiments or various modifications that can be thought of by those skilled in the art within the scope of the invention described in the claims are also understood to belong to the technical scope of the present invention.

[0160] [Example]

[0161] Hereinafter, the present invention will be specifically described with reference to Examples. In addition, the present invention is not limited to these Examples. In addition, "%" and "part" in the Examples represent "mass %" and "mass part" unless otherwise specified.

[0162] [Preparation of aqueous composition]

[0163] Aqueous compositions of Examples and Comparative Examples were prepared as follows.

[0164] (Synthesis of Polyamide)

[0165] First, a polyamide for use in the synthesis of a polyamide-polyether block polymer (including an example corresponding to the block copolymer (A1) of the present invention) is synthesized.

[0166] <Polyamide Synthesis Example 1>

[0167] In a 1-liter four-necked flask equipped with a stirring device, a temperature regulator, a water separator, and a nitrogen inlet tube, 354 parts (0.60 mol) of dimer acid (trade name "HARIDIMER (Japanese: ハリグイマー) 250", manufactured by Hallma Kasei Co., Ltd.) and 53.1 parts (15% by mass of the total carboxylic acid) of xylene were measured and heated to 50 °C. Next, 46.5 parts (0.40 mol) of hexamethylenediamine was gradually added to the four-necked flask and stirred at 150 °C for 60 minutes. Further, it was slowly heated to 175 °C for a dehydration reaction for 150 minutes to obtain polyamide P-1.

[0168] <Polyamide Synthesis Examples 2-4>

[0169] Except for changing the molar ratio of the dicarboxylic acid and diamine to those in Table 1, polyamides were synthesized in the same manner as in Polyamide Synthesis Example 1 to obtain polyamides P-2 to P-4.

[0170]

Table 1

[0171] Table 1 Synthesis Examples 1-4

[0172]

[0173]

[0174] (Synthesis of Polyamide-Polyether Block Polymer)

[0175] Next, using the polyamide P-1 or P-4 obtained as described above and the polyethers described in Table 2, polyamide-polyether block polymers of Synthesis Examples 5-16 were synthesized (see Table 2). In addition, without previously preparing polyamide, polyamide-polyether block polymers of Synthesis Examples 17-37 were synthesized using diamines and dicarboxylic acids as raw materials for polyamide and polyethers (see Table 3).

[0176] <Polyamide-Polyether Block Polymer Synthesis Example 5>

[0177] Using the same apparatus as in Polyamide Synthesis Example 1, 61.1 parts of polyamide P-1 of Synthesis Example 1 and 38.9 parts (1.00 mol relative to 1.00 mol of polyamide and 50 mol% relative to the acid equivalent) of STEAROXY (Japanese: ステア口キシ) PEG (trade name "blaunon (Japanese: ブラウノン) (registered trademark) SR-720", manufactured by Aoki Yushi Kogyo Co., Ltd.) were mixed. A dehydration reaction was carried out at 240 °C for 5 hours to obtain polyamide-polyether block polymer P-5.

[0178] <Polyamide-Polyether Block Polymer Synthesis Examples 6-16>

[0179] Polyamide-polyether block polymers P-6 to P-16 were obtained by synthesizing polyamide-polyether block polymers in the same manner as in Polyamide Synthesis Example 5, except that the molar ratio of polyamide P-1 or P-4 to the polyether raw material was changed to that shown in Table 2 (the polyether raw material is the equivalent relative to the polyamide). In addition, the reaction temperature of the dehydration reaction was appropriately adjusted within the range of 200 to 250° C., and the reaction time was appropriately adjusted within the range of 3 to 5 hours. In the case of easy coloration, hypophosphorous acid was added within the range of about 0.1 to 1.0 parts to suppress coloration.

[0180]

Table 2

[0181] Table 2 Synthesis examples 5 to 16

[0182]

[0183]

[0184] <Polyamide-polyether block polymer synthesis example 17>

[0185] In the same manner as in Polyamide Synthesis Example 1, 61.8 parts of high-purity dimer acid (trade name "Tsunodyme (Japanese: ツノグイム) (registered trademark) 395", manufactured by Tsunoh Food Industry Co., Ltd.), 4.3 parts of ethylenediamine (0.67 mol relative to 1.00 mol of high-purity dimer acid, 67 mol% of amine relative to acid equivalent), 33.9 parts of methoxy PEG (trade name "UNIOX (Japanese: ュニオツクス) (registered trademark) M-550", manufactured by NOF Corporation) (0.57 mol relative to 1.00 mol of high-purity dimer acid, 29 mol% relative to acid equivalent), and about 0.1 part of hypophosphorous acid for coloring prevention were mixed. Dehydration reaction was carried out at 230° C. for 5 hours to obtain a polyamide-polyether block polymer P-17.

[0186] <Polyamide-polyether block polymer synthesis examples 18 to 37>

[0187] Polyamide-polyether block polymers P-18 to P-37 were obtained by synthesizing polyamide-polyether block polymers in the same manner as in Polyamide Synthesis Example 17, except that the dicarboxylic acid, diamine, and polyether raw materials were changed to the molar ratios in Table 3 (molar ratios of raw materials, not functional group equivalents). In addition, the reaction temperature of the dehydration reaction was appropriately adjusted within the range of 200 to 250° C., the reaction time was appropriately adjusted within the range of 3 to 5 hours, and in the case of easy coloration, hypophosphorous acid was added within the range of about 0.1 to 1.0 parts to suppress coloration.

[0188]

Table 3

[0189] Table 3 (Part 1) Synthesis Examples 17 to 28

[0190]

[0191]

[0192]

Table 4

[0193] Table 3 (Part 2) Synthesis Examples 29 - 37

[0194]

[0195]

[0196] In addition, regarding using Tsunodyme 395 as the dicarboxylic acid in Synthesis Examples 1 - 37, for a, b, c, and p in formula (1), a = 1, b = 1, c = 1, and p = 1. Also, regarding using HARIDIMER 250 as the dicarboxylic acid in Synthesis Examples 1 - 37, for a, b, c, and p in formula (1), a = 1 - 11 (where a = 1 - 3 are the main components), b = 1 - 2 (where b = 1 is the main component), c = 1 - 2 (where c = 1 is the main component), p = 1 - 11 (where p = 1 - 3 is approximately the main component). Since m has a distribution, it cannot be specified, but the number average value can be obtained based on the acid / amine ratio. When the molar ratio of acid = molar ratio of amine + 1 is calculated, the molar ratio of amine directly becomes the number average value of m.

[0197] (Preparation Examples of Aqueous Compositions)

[0198] As described below, aqueous compositions of the Examples and Comparative Examples were prepared.

[0199] <Example 1>

[0200] 79.2 parts of deionized water was measured in a 500 mL four-necked flask equipped with a stirring device, a condenser, and a thermometer, and heated and maintained at 60 - 75°C. On the other hand, 15.0 parts of polyamide-polyether block polymer P-5, 5.3 parts of 2-butoxyethanol as a solvent, and 0.5 part of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. While stirring this liquid mixture, it was gradually added to the warm water in the flask. After the addition was completed, stirring was continued for 30 minutes while maintaining a temperature range of 50 - 80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-1.

[0201] <Examples 2 - 18 and 33 - 35>

[0202] Using the polyamide-polyether block polymers described in Table 5 at the blending ratios shown in Table 4, aqueous compositions E-2 to E-18 and E-33 to E-35 of Examples 2 to 18 and Examples 33 to 35 were obtained in the same manner as in Example 1.

[0203]

Table 5

[0204] Table 4 Examples 1 to 18, 33 to 35

[0205] Polyamide-polyether block polymer 15 2-Butoxyethanol 5.3 2-(Dimethylamino)ethanol x Deionized water 79.7-x total 100

[0206] ※x is the mass part of neutralization equivalent calculated based on acid value

[0207] <Example 19>

[0208] Using the same apparatus as in Example 1, 89.7 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 10.0 parts of polyamide-polyether block polymer P-6 and 0.3 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-19.

[0209] <Example 20>

[0210] Using the same apparatus as in Example 1, 74.5 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 15.0 parts of polyamide-polyether block polymer P-5, 10.0 parts of 4 mol of oxyalkylene adduct of 2-ethylhexanol as a surfactant, and 0.5 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-20.

[0211] <Example 21>

[0212] Using the same apparatus as in Example 1, 44.8 parts of deionized water were measured and heated to maintain a temperature of 60 - 75°C. On the other hand, 18.0 parts of polyamide - polyether block polymer P - 19, 36.0 parts of 2 - butoxyethanol, and 1.2 parts of 2 - (dimethylamino)ethanol as the neutralizing base were mixed at 120°C to obtain a liquid mixture. This liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining a temperature range of 50 - 80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E - 21.

[0213] <Example 22>

[0214] Using the same apparatus as in Example 1, 74.5 parts of deionized water were measured and heated to maintain a temperature of 60 - 75°C. On the other hand, 15.0 parts of polyamide - polyether block polymer P - 6, 10.0 parts of methoxy PEG (trade name "UNIOX (Japanese: ュ二オツクス) M - 400", manufactured by NOF Corporation) as a surfactant, and 0.5 parts of 2 - (dimethylamino)ethanol as the neutralizing base were mixed at 120°C to obtain a liquid mixture. This liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining a temperature range of 50 - 80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E - 22.

[0215] <Example 23>

[0216] Using the same apparatus as in Example 1, 30.0 parts of polyamide - polyether block polymer P - 13 and 70.0 parts of deionized water were measured. The mixture was heated to maintain a temperature of 60 - 75°C and stirring was continued for 30 minutes to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E - 23.

[0217] <Examples 24 and 26 - 32>

[0218] Using the same method as in Example 23 except that the polyamide - polyether block polymer was changed to P - 14 and P - 27 - P - 33, aqueous compositions E - 24, E - 26 - 32 were obtained respectively.

[0219] <Example 25>

[0220] Using the same apparatus as in Example 1, 10.0 parts of polyamide-polyether block polymer P-15 and 90.0 parts of deionized water were weighed. The mixture was heated to maintain 60-75° C. and stirred for 30 minutes to obtain a dispersion. After stirring, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-25.

[0221] <Example 36>

[0222] Using the same apparatus as in Example 1, 79.9 parts of deionized water were measured and heated to 50°C. On the other hand, 8.0 parts of polyamide-polyether block polymer P-36, 2.0 parts of B-4 described in Table 2 of Japanese Patent Publication No. 2012-111832, 5.0 parts of propylene glycol monomethyl ether, 4.0 parts of oxyalkylene adducts of 2-ethylhexanol as a surfactant, and 1.1 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining a temperature range of 40 to 55°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and heated in a thermostatic bath at 80°C for 20 hours to obtain an aqueous composition E-36.

[0223] <Example 37>

[0224] Using the same apparatus as in Example 1, 75.0 parts of deionized water were measured and heated to 50°C. On the other hand, 8.0 parts of polyamide-polyether block polymer P-36, 4.0 parts of hydrogenated castor oil, 7.0 parts of propylene glycol monomethyl ether, 5.0 parts of 4 mol of oxyalkylene adduct of 2-ethylhexanol as a surfactant, and 1.1 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature range of 40 to 55°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-37.

[0225] <Example 38>

[0226] Using the same apparatus as in Example 1, 78.5 parts of deionized water was measured and heated to maintain a temperature of 60 to 75 °C. On the other hand, 15.0 parts of polyamide-polyether block polymer P-5, 4.0 parts of propylene glycol monomethyl ether, 2.0 parts of diethylene glycol dibutyl ether, and 0.5 part of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120 °C to obtain a liquid mixture. While stirring this liquid mixture, it was gradually added to the warm water in the flask. After completion of the addition, stirring was continued for 30 minutes while maintaining a temperature range of 50 to 80 °C to obtain a dispersion. After completion of the stirring, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-38.

[0227] <Example 39>

[0228] Using the same apparatus as in Example 1, 76.5 parts of deionized water was measured and heated to maintain a temperature of 60 to 75 °C. On the other hand, 15.0 parts of polyamide-polyether block polymer P-5, 3.0 parts of 2-butoxyethanol, 5.0 parts of tetraethylene glycol dimethyl ether, and 0.5 part of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120 °C to obtain a liquid mixture. While stirring this liquid mixture, it was gradually added to the warm water in the flask. After completion of the addition, stirring was continued for 30 minutes while maintaining a temperature range of 50 to 80 °C to obtain a dispersion. After completion of the stirring, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-39.

[0229] <Example 40>

[0230] Using the same apparatus as in Example 1, 46.7 parts of deionized water was measured and heated to maintain a temperature of 60 to 75 °C. On the other hand, 22.0 parts of polyamide-polyether block polymer P-5, 3.5 parts of oleic acid, 7.0 parts of 2-butoxyethanol, and 20.8 parts of JEFFAMIN (registered trademark) M-1000 as a neutralizing base were mixed at 120 °C to obtain a liquid mixture. While stirring this liquid mixture, it was gradually added to the warm water in the flask. After completion of the addition, stirring was continued for 30 minutes while maintaining a temperature range of 50 to 80 °C to obtain a dispersion. After completion of the stirring, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-40.

[0231] <Example 41>

[0232] Using the same apparatus as in Example 1, 77.8 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 12.0 parts of polyamide-polyether block polymer P-5, 4.0 parts of polyamide-polyether block polymer P-37, 5.6 parts of 2-butoxyethanol, and 0.6 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-41.

[0233] <Example 42>

[0234] Using the same apparatus as in Example 1, 79.1 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 10.0 parts of polyamide-polyether block polymer P-5, 5.0 parts of polyamide-polyether block polymer P-37, 5.3 parts of 2-butoxyethanol, and 0.6 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-42.

[0235] <Example 43>

[0236] Using the same apparatus as in Example 1, 32.3 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 18.0 parts of polyamide-polyether block polymer P-34, 35.0 parts of 2-butoxyethanol, 14.0 parts of propylene glycol monomethyl ether, and 0.8 parts of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C to obtain a dispersion. After the stirring was completed, the dispersion was transferred to another container and allowed to stand at room temperature for 24 hours to obtain an aqueous composition E-43.

[0237] <Comparative Examples 1 to 3>

[0238] Aqueous compositions C-1 to C-3 of Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the polyamide-polyether block polymer was changed to polyamides P-1 to P-3, using the blending ratios shown in Table 4.

[0239] <Comparative Example 4>

[0240] Using the same apparatus as in Example 1, 30.0 parts of polyamide P-4, 6.1 parts of 2-(dimethylamino)ethanol as a neutralizing base, and 63.9 parts of deionized water were measured. The mixture was heated to maintain 60-75°C and stirred for 30 minutes, but it did not become uniform. Since a uniform aqueous composition could not be obtained, the subsequent test was cancelled.

[0241] The aqueous compositions obtained as described above are summarized in Table 5 below.

[0242]

Table 6

[0243] Table 5 Summary of aqueous compositions

[0244]

[0245]

[0246] <Comparative Example 5 (DMDG gel composition corresponding to E-1)>

[0247] 15.0 parts of polyamide-polyether block polymer P-5 and 85.0 parts of diethylene glycol dimethyl ether (DMDG) were weighed in a 500 mL four-necked flask equipped with a stirring device, a cooling tube, and a thermometer, and stirred and dissolved for 30 minutes while maintaining a temperature range of 80 to 120° C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours to obtain a DMDG gel composition corresponding to aqueous composition E-1.

[0248] <Comparative Examples 6 to 33 (DMDG gel compositions corresponding to E-2 to E-22, E-33 to E-35, E-38 to E-40, and E-43)>

[0249] DMDG gel compositions of Comparative Examples 6 to 33 were obtained in the same manner as in Comparative Example 5 except that the polyamide-polyether block polymers were changed to P-5 to P-12, P-16 to P-26, P-34, and P-35.

[0250] <Comparative Example 34 (DMDG gel composition corresponding to E-36)>

[0251] Using the same apparatus as in Comparative Example 5, 12.0 parts of polyamide-polyether block polymer P-36, 3.0 parts of B-4 described in Table 2 of JP-2012-111832A, and 85.0 parts of DMDG were weighed, and stirred and dissolved for 30 minutes while maintaining a temperature range of 80 to 120° C. After stirring, the solution was transferred to another container and allowed to stand at room temperature for 24 hours to obtain a DMDG gel composition corresponding to aqueous composition E-36.

[0252] <Comparative Example 35 (DMDG gel composition corresponding to E-37)>

[0253] Using the same apparatus as in Comparative Example 5, 10.0 parts of polyamide-polyether block polymer P-36, 5.0 parts of hydrogenated castor oil, and 85.0 parts of DMDG were weighed and dissolved while stirring for 30 minutes while maintaining the temperature in the range of 80 to 120° C. After stirring, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby obtaining a DMDG gel composition corresponding to aqueous composition E-37.

[0254] <Comparative Example 36 (DMDG gel composition corresponding to E-41)>

[0255] Using the same apparatus as in Comparative Example 5, 11.3 parts of polyamide-polyether block polymer P-5, 3.8 parts of polyamide-polyether block polymer P-37, and 85.0 parts of DMDG were weighed and dissolved while stirring for 30 minutes while maintaining the temperature in the range of 80 to 120° C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby obtaining a DMDG gel composition corresponding to aqueous composition E-41.

[0256] <Comparative Example 37 (DMDG gel composition corresponding to E-42)>

[0257] Using the same apparatus as in Comparative Example 5, 10.0 parts of polyamide-polyether block polymer P-5, 5.0 parts of polyamide-polyether block polymer P-37, and 85.0 parts of DMDG were weighed and dissolved for 30 minutes while maintaining the temperature in the range of 80 to 120° C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby obtaining a DMDG gel composition corresponding to aqueous composition E-42.

[0258] <Comparative Example 38 (HG gel composition corresponding to E-1)>

[0259] 15.0 parts of polyamide-polyether block polymer P-5 and 85.0 parts of 2-methyl-2,4-pentanediol (also known as hexylene glycol: HG) were weighed in a 500 mL four-necked flask equipped with a stirring device, a cooling tube, and a thermometer, and stirred and dissolved for 30 minutes while maintaining a temperature range of 80 to 120°C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby attempting to prepare an HG gel composition corresponding to the aqueous composition E-1, but it did not gel. Since it did not gel, there was no possibility of exerting the viscosity adjustment function (viscosity imparting effect), so the subsequent test was cancelled.

[0260] <Comparative Examples 39 to 66 (HG gel compositions corresponding to E-2 to E22, E-33 to E-35, E-38 to E-40, and E-43)>

[0261] The same method as in Comparative Example 38 was used except that the polyamide-polyether block polymer was changed to P-5 to P-12, P-16 to P-26, P-34, and P-35, and HG gel compositions were prepared. The HG gel composition corresponding to E-9 gelled, but the other compositions did not gel. Since the compositions that did not gel did not have the possibility of exerting the viscosity adjustment function, the subsequent tests were cancelled.

[0262] <Comparative Example 67 (HG gel composition corresponding to E-36)>

[0263] Using the same apparatus as in Comparative Example 38, 12.0 parts of polyamide-polyether block polymer P-36, 3.0 parts of B-4 described in Table 2 of JP-2012-111832A, and 85.0 parts of HG were weighed and dissolved for 30 minutes while maintaining the temperature in the range of 80 to 120° C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby obtaining an HG gel composition corresponding to aqueous composition E-36.

[0264] <Comparative Example 68 (HG gel composition corresponding to E-37)>

[0265] Using the same apparatus as in Comparative Example 38, 10.0 parts of polyamide-polyether block polymer P-36, 5.0 parts of hydrogenated castor oil, and 85.0 parts of HG were weighed and dissolved while stirring for 30 minutes while maintaining the temperature in the range of 80 to 120° C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby obtaining an HG gel composition corresponding to aqueous composition E-37.

[0266] <Comparative Example 69 (HG gel composition corresponding to E-41)>

[0267] Using the same apparatus as in Comparative Example 38, 11.3 parts of polyamide-polyether block polymer P-5, 3.8 parts of polyamide-polyether block polymer P-37, and 85.0 parts of HG were weighed and dissolved while being stirred for 30 minutes while maintaining a temperature range of 80 to 120°C. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours, thereby attempting to prepare an HG gel composition corresponding to aqueous composition E-41, but gelation did not occur. Since gelation did not occur, there was no possibility of exerting the viscosity adjustment function (viscosity imparting effect), so the subsequent test was cancelled.

[0268] <Comparative Example 70 (HG gel composition corresponding to E-42)>

[0269] Using the same apparatus as in Comparative Example 38, 10.0 parts of polyamide-polyether block polymer P-5, 5.0 parts of polyamide-polyether block polymer P-37, and 85.0 parts of HG were weighed and dissolved while maintaining the temperature range of 80 to 120° C. for 30 minutes under stirring. After the stirring was completed, the solution was transferred to another container and allowed to stand at room temperature for 24 hours to attempt to prepare an HG gel composition corresponding to aqueous composition E-42, but gelation did not occur. Since gelation did not occur, there was no possibility of exerting the viscosity adjustment function (viscosity imparting effect), so the subsequent test was cancelled.

[0270] <Comparative Example 71>

[0271] Using the same apparatus as in Example 1, 89.0 parts of deionized water were measured and heated to maintain 60-75°C. On the other hand, 10.0 parts of polyamide P-1 and 1.0 part of 2-(dimethylamino)ethanol as a neutralizing base were mixed at 120°C to obtain a liquid mixture. The liquid mixture was gradually added to the warm water in the flask while stirring. After the addition was completed, stirring was continued for 30 minutes while maintaining the temperature in the range of 50-80°C, but it did not become uniform. Since a uniform aqueous composition could not be obtained, the subsequent test was cancelled.

[0272] (Preparation of 3% masterbatch)

[0273] A 3% jellyfish batch is prepared using the aqueous composition or gel composition of each embodiment and comparative example. Each composition is measured, and a neutralization equivalent of 2-(dimethylamino)ethanol is added to each unneutralized composition, and deionized water is added so that the solid content of the composition is 3%. The mixture is stirred with a laboratory disperser, and the rotation speed is gradually increased to prevent air from being drawn in. Disperse at a maximum of 2500 rpm for 10 minutes to prepare a 3% jellyfish batch. Among them, since E-40 to E-43 could not be dispersed within 10 minutes, an additional 10 to 20 minutes of dispersion were performed to prepare a 3% jellyfish batch. The formulation of the 3% jellyfish batch is shown in Table 6.

[0274]

Table 7

[0275] Table 6 3% masterbatch preparation

[0276]

[0277] [Test on Viscosity Adjustment Function: Evaluation Method and Evaluation Results]

[0278] The aqueous compositions or gel compositions of Examples and Comparative Examples obtained as described above were subjected to performance tests on viscosity adjustment function as described below using the 3% water-jelly batch obtained as described above (Test Examples 1 to 4).

[0279] (Test Example 1: Evaluation in aqueous dispersion)

[0280] This test example is an evaluation in an aqueous dispersion in which the aqueous composition or gel composition of the example and the comparative example was diluted with water and dispersed.

[0281] <Preparation of Aqueous Dispersion>

[0282] Deionized water was stirred with a laboratory disperser, and a predetermined amount of the 3% water-jelly material obtained as described above was added and dispersed with a laboratory disperser (800 to 1500 rpm x 10 minutes). Table 7 shows the preparation of the aqueous dispersion.

[0283]

Table 8

[0284] Table 7 Aqueous Dispersion Preparation

[0285] 3% masterbatch 10 Deionized water 50 total 60

[0286] <Viscosity Evaluation>

[0287] The steady flow viscosity of the aqueous dispersion was measured at 25°C using a rheometer with a 60 mm cone-shaped fixture. -1 Up to 1000s -1 After the measurement (Low-High measurement), 1000s-1 To 0.01 s -1 Determination (High-Low determination). Read the shear rate of the High-Low determination at 0.1 s -1 and 1000 s -1 and viscosity. Table 8 shows the results of the viscosity evaluation in this test example. In addition, in Table 8, the notation "poor dispersion" indicates that separation or coarse particles have occurred in the liquid. Further, the notation "below the measurement limit" indicates that the viscosity is so low that it cannot be measured by the device. Furthermore, the notation "not gelled" indicates that the test was not conducted because a gel composition could not be prepared.

[0288]

Table 9

[0289] Table 8 Viscosity evaluation of the aqueous dispersion

[0290]

[0291]

[0292] (Test Example 2: Evaluation I in the emulsion resin liquid)

[0293] This test example is an evaluation in an emulsion resin liquid obtained by dispersing the aqueous compositions or gel compositions of the examples and comparative examples with an emulsion resin.

[0294] <Preparation of the emulsion resin liquid>

[0295] According to the formulation described in Table 9, after stirring and mixing an emulsion resin (trade name "Mowinyl (Japanese: モビ二一ル) (registered trademark) 7110", manufactured by Japan Coating Resin Co., Ltd.), deionized water, and dodecyl alcohol ester, the 3% masterbatch obtained as described above was added and dispersed with a laboratory disperser (900 - 1500 rpm × 10 minutes).

[0296]

Table 10

[0297] Table 9 Emulsion resin liquid formulation I

[0298] Mowinyl 7110 76.1 Deionized water 2.2 Dodecyl alcohol ester 8.8 3% masterbatch 13.3 total 100.4

[0299] <Viscosity evaluation>

[0300] The steady flow viscosity of the emulsion resin liquid was measured at 25°C using a rheometer equipped with a conical fixture set at 60 mm. After performing the determination at a shear rate of 0.01 s -1 to 1000 s -1 and then performing the determination from 1000 s -1 to 0.01 s -1Read the shear rate of High-Low measurement at 0.1s. -1 and 1000s -1 The results of viscosity evaluation in this test example are shown in Table 10. In addition, in Table 10, the record of "poor dispersion" means that separation or coarse particles are generated in the liquid. In addition, the record of "ungelled" means that the test was not carried out because a gel composition could not be prepared.

[0301]

Table 11

[0302] Table 10 Evaluation of viscosity of emulsion resin liquid I

[0303]

[0304] (Test Example 3: Evaluation in Dispersed Resin Liquid)

[0305] This test example is an evaluation in a dispersion resin liquid in which the aqueous composition or gel composition of the example and the comparative example is diluted with a dispersion resin and dispersed.

[0306] <Preparation of Dispersed Resin Liquid>

[0307] According to the formulation described in Table 11, after stirring and mixing the dispersion resin (trade name "HYDRAN (Japanese: ハイドラン) (registered trademark) WLS-210", manufactured by DIC Corporation), deionized water, glycerin, and 2-propanol, add the 3% masterbatch obtained as described above and disperse it with a laboratory disperser (900~1500rpm×10 minutes).

[0308]

Table 12

[0309] Table 11 Dispersed resin liquid preparation

[0310]

[0311]

[0312] <Viscosity Evaluation>

[0313] The steady flow viscosity of the dispersed resin liquid was measured at 25°C using a rheometer with a 60 mm cone-shaped fixture. -1 Up to 1000s -1 After the measurement (Low-High measurement), 1000s -1 To 0.01s -1 Read the shear rate of High-Low measurement at 0.1s. -1 and 1000s -1The viscosity of the mixture was 0.0447 W / m. The viscosity of the mixture was 0.0347 W / m. The viscosity of the mixture was 0.02 ... Table 12 shows the results of the viscosity evaluation in this test example. In Table 12, "poor dispersion" indicates that separation or coarse particles were generated in the liquid. In addition, "ungelled" indicates that the test was not performed because a gel composition could not be prepared.

[0314]

Table 13

[0315] Table 12 Evaluation of viscosity of dispersed resin liquid

[0316]

[0317] (Test Example 4: Evaluation II in Emulsion Resin Liquid)

[0318] This test example is an evaluation in which the aqueous composition or gel composition of the examples and comparative examples was diluted with an emulsion resin different from that of Test Example 2 and dispersed in an emulsion resin liquid.

[0319] <Preparation of Emulsion Resin Liquid>

[0320] According to the formulation described in Table 13, the emulsion resin (trade name "POLYDUREX (Japanese: ポリデユレツクス) (registered trademark) G620S, manufactured by Asahi Kasei Corporation), deionized water, and dodecanol ester were stirred and mixed, and then the 3% masterbatch obtained as described above was added and dispersed using a laboratory disperser (900-1500 rpm×10 minutes).

[0321]

Table 14

[0322] Table 13 Emulsion resin liquid preparation II

[0323] POLYDUREX G620S 76.1 Deionized water 7.5 Dodecyl alcohol ester 3.5 3% masterbatch 13.3 total 100.4

[0324] <Viscosity Evaluation>

[0325] The steady flow viscosity of the emulsion resin liquid was measured at 25°C using a rheometer with a 60 mm cone-shaped fixture. -1 Up to 1000s -1 After the measurement (Low-High measurement), 1000s -1 To 0.01s -1 Read the shear rate of High-Low measurement at 0.1s. -1 and 1000s -1 The viscosity of the mixture was 0.0447 W / m. The viscosity of the mixture was 0.0347 W / m. The viscosity of the mixture was 0.02 ... Table 14 shows the results of the viscosity evaluation in this test example. In addition, in Table 14, the record of "poor dispersion" indicates that separation or coarse particles were generated in the liquid. In addition, the record of "ungelled" indicates that the test was not performed because a gel composition could not be prepared.

[0326]

Table 15

[0327] Table 14 Evaluation II of viscosity of emulsion resin liquid

[0328]

[0329] [Review of evaluation results]

[0330] The polyamide and polyamide-polyether block polymers have the characteristics of suppressing the viscosity increase at a high shear rate (1000 s-1 in the above test example) and increasing the viscosity at a low shear rate (0.1 s-1 in the above test example). -1 ) is characterized by an increase in viscosity. This viscosity is a feature suitable for spraying, and is advantageous in preventing sedimentation, preventing sagging, improving the orientation of glossy pigments known as angular color variability, and improving the appearance of the coating film. In the evaluated examples, the polyamide-polyether block polymers P-5 to P-12 and P-16 used for E-1 to E-8, E-19, E-20, E-22, and E-33 are obtained by reacting the polyether portion with the polyamide P-1 used for C-1. The 0.1s -1 The viscosity is higher than that of C-1, so it can be considered to have a more excellent viscosity adjustment function. Compared with other comparative examples C-2 to C-3, the aqueous composition using the polyamide-polyether block polymer shows a generally high viscosity imparting effect. Among them, regarding E-22 in the aqueous dispersion, although it has an advantage over C-1 with the same polyamide skeleton, the result is inferior to C-2 and C-3. E-22 is a polyamide-polyether block polymer using P-6, which is the same as E-2, but contains methoxy PEG in the formulation, and R4 is 2 (R4O) nThe mass % exceeds the prescribed amount, so it is believed that the viscosity imparting effect is reduced. In addition, E-19 is only the amine salt of the polyamide-polyether block polymer P-6 and water without the deployment of a solvent, but an aqueous composition can be made. Here, there is a situation where it is not desired to bring a solvent contained in a viscosity modifier into a coating, etc., and E-19 is an aqueous composition having a viscosity adjustment function that can correspond to this situation. The viscosity imparting effect of the aqueous resin composition of E-19 shows an effect equal to or higher than that of C-1 containing a solvent. On the other hand, in the case of using a polyamide P-1 as a structure after removing the polyether portion from the polyamide-polyether block polymer used for E-19, a uniform aqueous composition cannot be made without a solvent (refer to Comparative Example 71). This indicates that the dispersibility of polyamide P-1 relative to water is insufficient, and a solvent is required to disperse polyamide P-1 in water. In the case of polyamide-polyether block polymer P-6, there is no need to contain a solvent in order to be dispersed in water, and it has a sufficient viscosity adjustment function. The aqueous compositions of Examples and Comparative Examples all maintained a viscosity at 1000 s-1 that was similar to that of Blank (containing no polyamide and polyamide-polyether block polymer).

[0331] When the DMDG gel composition and the HG gel composition were used for water systems, the dispersion was poor, or even if it was dispersed, the effect was low compared with the aqueous composition, or no gelation was obtained.

[0332] (Preparation of 3% resin masterbatch)

[0333] Use Example 6 (E-6) and Comparative Example 1 (C-1) to make a 3% resin masterbatch. Neutralize the dispersion resin (trade name "NeoPac (registered trademark) E-123", manufactured by Covestro (Netherlands) BV) with 2-(dimethylamino)ethanol, and add each composition so that the solid content is 3%. Stir the mixture with a laboratory disperser, gradually increasing the speed so that air is not drawn in. Disperse at a maximum of 2500 rpm for 10 minutes to make a 3% resin masterbatch. Table 15 shows the formulation of the 3% resin masterbatch.

[0334]

Table 16

[0335] Table 15 3% resin masterbatch preparation

[0336] NeoPac E-123 79.9 2-(Dimethylamino)ethanol 0.1 Aqueous composition 20.0 total 100.0

[0337] [Test on color flop: evaluation method and evaluation results]

[0338] For the aqueous compositions of the examples and comparative examples obtained as described above, using the 3% resin masterbatch obtained as described above and an acrylic viscosity modifier as a comparison object (trade name "RHEOVIS (registered trademark) AS1130" (hereinafter, simply referred to as "acrylic A".), manufactured by BASF Societas Europeae), the following performance test on flop (Test Example 5) was conducted as follows.

[0339] (Test Example 5: Evaluation in an aqueous coating composition containing a metallic pigment)

[0340] This test example is an evaluation in an aqueous coating composition containing the aqueous compositions of the examples and comparative examples and an aluminum pigment as a metallic pigment.

[0341] <Preparation of aluminum paste>

[0342] According to the formulation described in Table 16, an aluminum pigment (trade name "EMERAL (Japan: 工メラル) (registered trademark) EMR-D6340", manufactured by Toyo Aluminum Co., Ltd.), a dispersant (trade name "DISPARLON (デイスパ口ン) (registered trademark) AQ-320", manufactured by Kusumoto Chemicals, Ltd.), and deionized water were stirred and mixed with a laboratory disperser to obtain an aluminum paste.

[0343]

Table 17

[0344] Table 16 Aluminum paste formulation

[0345] EMERAL EMR-D6340 5.1 DISPARLON AQ-320 0.3 Deionized water 9.5 total 14.9

[0346] <Preparation of aqueous coating composition>

[0347] According to the formulation described in Table 17, after stirring and mixing a dispersion resin (trade name "NeoPac E-123", manufactured by Covestro (Netherlands) B.V.), dipropylene glycol monobutyl ether, 2-(dimethylamino)ethanol, deionized water, and a wetting agent (trade name "DISPARLON (Japanese: デイスパロン) AQ-7120", manufactured by Kusumoto Chemicals, Ltd.), as a viscosity modifier, the 3% masterbatch obtained as described above or acrylic A was added, and dispersion was carried out with a laboratory disperser (1500 - 2000 rpm × 10 minutes). Further, the rotation speed of the laboratory disperser was changed to 1000 rpm, and the aluminum paste obtained as described above was added and stirred for 10 minutes.

[0348]

Table 18

[0349] Table 17 Aluminum coating formulation

[0350]

[0351]

[0352] x is the value of solid content 0.4 or 0.3

[0353] The next day, the obtained water-based coating composition was diluted with deionized water using Ford Cup #4 at 25°C for 20 seconds. At this time, the solid content of the coating also changes greatly when the dilution amount increases, so the amount of deionized water used for dilution is not more than 5% relative to the mass of the coating. When the acrylic A is added in the same solid content as the water-based composition, the deionized water required for dilution exceeds 5% relative to the mass of the coating, so the amount added is reduced and the same operation is repeated.

[0354] <Painting test>

[0355] In an environment of 23°C and 50% RH, the tinplate was coated using an automatic sprayer (trade name "XY Coating Machine", manufactured by NCC Corporation). The coating was performed by adjusting the discharge volume so that the dry film thickness was 11 to 14 μm. After standing for 5 minutes, it was dried in a constant temperature bath at 80°C for 20 minutes for curing. A portable multi-angle spectrometer (trade name "MA-T12", manufactured by X-Rite INCORPORATED) was used to measure the brightness (L*) of the cured coating at observation angles of 15°, 45°, and 110°. In addition, the flop index (FI) was calculated using the following formula (3). The higher the flop index, the better the flop property.

[0356] FI=2.69×(L* 15 -L* 110 ) 1.11 / (L* 45 ) 0.85 (3)

[0357] <Viscosity Evaluation>

[0358] The steady-state viscosity of the diluted water-based coating composition was measured at 25° C. using a rheometer with a 60 mm cone-shaped fixture. -1 Up to 1000s -1 After the measurement (Low-High measurement), 1000s -1 To 0.01s -1 Read the shear rate of High-Low measurement at 0.1s. -1 and 1000s -1 Table 18 summarizes the results of the viscosity evaluation in this test example and the results of the above-mentioned coating test.

[0359]

Table 19

[0360] Table 18 Test of angle-dependent color

[0361] result

[0362]

[0363] Since Blank's Ford Cup #4 had 12 seconds, no dilution was done

[0364] [Summary and review of evaluation results]

[0365] Polyamide and polyamide-polyether block polymers suppress high shear rates (1000 s in the above test example) -1 ) while increasing the viscosity at a low shear rate (0.1s in the above test example). -1 ) increases in viscosity. It is believed that this viscosity characteristic shows high angular flop. In addition, the aqueous composition E-6 using the polyamide-polyether block polymer P-10 has a better angular flop than the aqueous composition C-1 using the polyamide P-1. It is believed that by using the aqueous composition using the polyamide-polyether block polymer as a viscosity modifier, a coating film showing more excellent angular flop can be produced.

[0366] [Test on the effect of combined use with other viscosity modifiers: evaluation method and evaluation results]

[0367] The aqueous compositions of the examples obtained as described above were subjected to performance tests on the effects of combination with other viscosity modifiers as follows using the 3% water concentrate obtained as described above (Test Examples 6 to 8).

[0368] (Test Example 6: Evaluation in aqueous dispersion)

[0369] This test example is an evaluation in an aqueous dispersion obtained by diluting the aqueous composition of the example with water and mixing other viscosity modifiers. As viscosity modifiers, a urethane-based viscosity modifier (trade name "ADEKA NOL (Japanese: アデカノール) (registered trademark) UH-752" (hereinafter simply referred to as "urethane-based A"), trade name "ADEKANOL (Japanese: アデカノール) UH-540" (hereinafter simply referred to as "urethane-based B"), both manufactured by ADEKA CORPORATION), (trade name "ACRYSOL RM-2020NPR" (hereinafter simply referred to as "urethane-based C"), manufactured by DOW CHEMICAL COMPANY), and an acrylic-based viscosity modifier (trade name "DISPARLON (Japanese: デイスパロン) AQ-021" (hereinafter simply referred to as "acrylic-based B"), manufactured by Kusumoto Chemicals, Ltd.) were used in combination with the aqueous dispersion of the aqueous composition of the example.

[0370] <Preparation of Aqueous Dispersion>

[0371] Deionized water was stirred with a laboratory disperser, a specified amount of the 3% water-based mother liquor obtained as described above was added, and after further adding a specified amount of the other viscosity modifiers used in combination, dispersion was carried out with a laboratory disperser (800 - 1500 rpm × 10 minutes). The formulation of the aqueous dispersion is shown in Table 19. In addition, as a comparison object, an aqueous dispersion diluted with water so that each solid content was 1.0% was similarly prepared.

[0372]

Table 20

[0373] Table 19 Formulation of Aqueous Dispersion with Combined Viscosity Modifiers

[0374]

[0375]

[0376] x is the value with a solid content of 0.3, and y is the value with a solid content of 0.12

[0377] <Viscosity Evaluation>

[0378] The steady flow viscosity of the emulsion resin liquid was measured at 25°C using a rheometer equipped with a conical fixture set at 60 mm. After performing measurements at a shear rate of 0.01 s -1 to 1000 s -1 (Low-High measurement), measurements were performed from 1000 s -1 to 0.01 s -1 (High-Low measurement). The shear rates of 0.1 s -1 and 1000 s-1 Viscosity. The results of the viscosity evaluation in this test example are shown in Table 20.

[0379]

Table 21

[0380] Viscosity Evaluation of Emulsion Resin Liquid with Viscosity Modifier Blended

[0381]

[0382] (Test Example 7: Evaluation in Emulsion Resin Liquid)

[0383] This test example is an evaluation in an emulsion resin liquid in which another viscosity modifier is mixed in an emulsion resin liquid obtained by dispersing the aqueous composition of the example with an emulsion resin. As the viscosity modifier, an amide-based viscosity modifier (Production Example S1 described in International Publication No. 2022 / 097747 (hereinafter simply referred to as "amide-based")) is used in combination with the emulsion resin liquid of the aqueous composition of the example.

[0384] <Preparation of Emulsion Resin Liquid>

[0385] According to the formulation described in Table 21, after stirring and mixing emulsion resin (trade name "Mowinyl (Japanese: モビニ一ル) 7110", manufactured by Japan Coating Resin Co., Ltd.), deionized water, and dodecyl alcohol ester, 3% resin masterbatch obtained as described above is added, and a specified amount of other viscosity modifier used in combination (in this specification and the table, it may also be described as "rheology control agent") is further added, and then dispersed with a laboratory disperser (900 - 1500 rpm × 10 minutes). In addition, emulsion resin liquids with a solid content of 0.4% for each are prepared in the same manner as comparative objects.

[0386]

Table 22

[0387] Table 21 Formulation of Emulsion Resin Liquid with Viscosity Modifier Blended

[0388] Mowinyl 7110 76.1 Deionized water 5.5-x Dodecyl alcohol ester 8.8 Other rheology control agents x 3% masterbatch 10.0 total 100.4

[0389] x is the value with a solid content of 0.1

[0390] <Viscosity Evaluation (Recovery Measurement)>

[0391] The viscosity recovery of the emulsion resin liquid is measured at 25 °C using a rheometer with a conical fixture set at 60 mm. According to the procedure of measuring for 1 minute at a shear rate of 0.1 s -1 measuring for 10 seconds at a shear rate of 1000 s -1 measuring for 1 minute at a shear rate of 0.1 s -1Measure the viscosity at 1-second intervals for 2 minutes (Step 3). Read the viscosity 5 seconds after Step 3 starts. Table 22 shows the results of the viscosity evaluation in this test example.

[0392]

Table 23

[0393] Table 22 Viscosity Evaluation of Emulsion Resin Liquid with Viscosity Adjuster

[0394] Viscosity 5s after step 3 [mPa·s] E-4 906 Amide series 212 Amide series / E-4(1 / 3) 966

[0395] (Test Example 8: Evaluation in Dispersion Resin Liquid)

[0396] This test example is an evaluation in a dispersion resin liquid in which other viscosity adjusters are mixed in a dispersion resin liquid obtained by dispersing the aqueous composition of the example with a dispersion resin. As the viscosity adjuster, an acrylic acid-based viscosity adjuster (trade name “DISPARLON (Japanese: デイスパ口ン) AQ-001” (hereinafter simply referred to as “acrylic acid-based C”.), manufactured by Kusumoto Chemicals, Ltd.) is used in combination with the dispersion resin liquid of the aqueous composition of the example.

[0397] (Production of Dispersion Resin Liquid)

[0398] According to the formulation described in Table 23, after stirring and mixing the dispersion resin (trade name “HYDRAN (Japanese: ハイドラン) WLS-210”, manufactured by DIC Corporation), deionized water, glycerin, and 2-propanol, the 3% resin masterbatch obtained as described above is added, and after further adding a specified amount of other viscosity adjusters used in combination, it is dispersed with a laboratory disperser (900 - 1500 rpm × 10 minutes). In addition, dispersion resin liquids with a solid content of 0.4% for each are similarly produced as comparative objects.

[0399]

Table 24

[0400] Table 23 Formulation of Dispersion Resin Liquid with Viscosity Adjuster

[0401] 5 / 5 deployment 1 / 7 deployment HYDRAN WLS-210 33.3 33.3 Deionized water 31.9-x 26.9-y glycerin 6.9 6.9 2-Propanol 21.6 21.6 Other rheology control agents x y 3% masterbatch 6.7 11.7 100.4 100.4

[0402] x is the value with a solid content of 0.3, and y is the value with a solid content of 0.05

[0403] (Viscosity Evaluation (Recovery Measurement))

[0404] Perform the viscosity recovery measurement of the dispersion resin liquid at 25°C using a rheometer with a conical fixture set at 60 mm. According to the following steps: measure for 1 minute (Step 1) at a shear rate of 0.1 s -1 measure for 10 seconds (Step 2) at a shear rate of 1000 s -1 measure for 10 seconds (Step 2) at a shear rate of 0.1 s -1The viscosity was measured at 1 second intervals in the order of 2 minutes (step 3). The viscosity was read 10 seconds after step 3. Table 24 shows the results of the viscosity evaluation in this test example.

[0405]

Table 25

[0406] Table 24 Evaluation of viscosity of emulsion resin liquid using viscosity modifier

[0407] Viscosity 10s after step 3 [mPa·s] E-10 282 Acrylic C 25 Acrylic C / E-10(2 / 2) 329 Acrylic C / E-10(1 / 7) 431

[0408] [Summary and review of evaluation results]

[0409] Compared with the viscosity of the aqueous composition using only polyamide-polyether block polymer (having viscosity adjustment function) or other viscosity modifiers, in the case of using them together, a viscosity higher than the case of using only any one is shown. Usually, since the total amount of viscosity modifiers does not change even if the aqueous composition using polyamide-polyether block polymer and other viscosity modifiers are used together, the viscosity is a value near the additive average. Alternatively, since any one or both viscosity modifiers do not become the amount required for presenting viscosity, a viscosity lower than the additive average is shown. However, by using the aqueous composition using polyamide-polyether block polymer and other viscosity modifiers together, a viscosity higher than the additive average is obtained, so it can be considered that the aqueous composition using polyamide-polyether block polymer is easy to show special interactions with other viscosity modifiers.

[0410] [Test on Dispersion Function: Evaluation Method and Evaluation Results]

[0411] Using the aqueous compositions of Examples obtained as described above, performance tests on the dispersing function were performed as follows (Test Examples 9 and 10).

[0412] (Test Example 9: Dispersion Function to CNT)

[0413] This test example is a test example for evaluating the dispersion function of the aqueous composition of the example to CNTs.

[0414] According to the formulation described in Table 25, the aqueous composition (E-23~E-32), deionized water, and CNT powder (trade name "TUBALL (registered trademark) 01RW03", manufactured by OCSiAl) were measured and pre-dispersed (10000~11000rpm×2 hours) using a precision emulsifying disperser (trade name "CLEARMIX (Japanese: クレアミツクス) (registered trademark) CLM-0.8S", manufactured by M·TECHNIQUE Co., Ltd.). Furthermore, a wet medium-free atomization device (trade name "Nanovater (Japanese: ナノヴエイタ) (registered trademark) C-ES", manufactured by Yoshida Machinery Co., Ltd.) was used to formally disperse the dispersion after the preliminary dispersion (the discharge volume set by the device was 30 in the first return, the discharge pressure was 30 MPa in the second return, and 70 MPa in the 3rd to 13th return) to obtain a CNT dispersion.

[0415]

Table 26

[0416] Table 25 CNT dispersion preparation

[0417] E-23, E-24, E-26 to E-32 E-25 Aqueous composition 3.3 10.0 Deionized water 96.7 90.0 CNT 0.5 0.5 total 100.5 100.5

[0418] <Dispersibility Evaluation>

[0419] The CNT dispersion obtained as described above was diluted with deionized water so that the CNT concentration was 0.001%. The optical density was measured using a spectrophotometer. The dispersion performance was evaluated by comparing the optical density at 500 nm. When the optical density was 0.45 or more and less than 0.50, it was judged to be "good dispersibility", and when the optical density was 0.50 or more, it was judged to be "very good dispersibility". The evaluation results are shown in Table 26.

[0420]

Table 27

[0421] Table 26 Evaluation results of CNT dispersion

[0422]

[0423]

[0424] (Test Example 10: Dispersion Function to Organic Pigments)

[0425] This test example is a test example for evaluating the dispersion function of the aqueous composition of the example to the organic pigment.

[0426] According to the formulation described in Table 27, as the organic pigment, measure cyan: trade name "Heliogen (registered trademark) Blue D7088", or magenta (Japanese: マゼンタ): trade name "Cinquasia (registered trademark) Magentan D4500J" (both are manufactured by Sun Chemical Ltd.), deionized water, aqueous compositions (E-26, E-27), defoamer (trade name "DISPARLON (Japanese: デイスパ口ン) (registered trademark) AQ-7533N", manufactured by Kusumoto Chemical Co., Ltd.). Further, add 400 g of zirconia beads with a diameter of 0.3 mm. After dispersing for 3 hours using a paint shaker, separate from the zirconia beads to obtain an organic pigment dispersion.

[0427] [Table 28]

[0428] Table 27 Formulation of Organic Pigment Dispersion

[0429] Organic Pigments 18.7 Deionized water 61.6 Aqueous composition 18.7 DISPARLON AQ-7533N 1.0 total 100.0

[0430] <Dispersion Evaluation>

[0431] Evaluate the organic pigment dispersion obtained as described above through a viscosity and particle size distribution system. The viscosity is measured at 25°C using a rheometer with a conical fixture set at 60 mm for the shear rate of the organic pigment dispersion from 1 s -1 to 100 s -1 (Low-High measurement) for steady flow measurement. Use a dynamic light scattering particle size distribution measuring device to measure the particle size distribution. Evaluate the dispersion performance through the viscosity at a shear rate of 10 s -1 and D50. When the viscosity is below 100 mPa·s, it is judged as "good dispersion", and when D50 is below 0.3 μm, it is judged as "good dispersion". The evaluation results are shown in Table 28.

[0432] [Table 29]

[0433] Table 28 Evaluation Results of Organic Pigment Dispersion

[0434]

[0435] [Examination of Evaluation Results]

[0436] Regarding the dispersing function, while comparative example 4 could not produce a 30% aqueous dispersion, all examples except E-25 were adjusted to 30% concentration and showed good dispersibility for the evaluated CNTs and organic pigments. Comparative example 4 used a polyamide with the highest acid value (=high hydrophilicity) among P-1 to P-4, but the hydrophilicity was insufficient.

[0437] E-25, which has 18 carbon atoms at the terminal (R3), could not be prepared into a 30% aqueous dispersion, but it was possible to test it in a 10% aqueous dispersion. The CNT dispersion performance of E-25 was slightly inferior to that of other aqueous dispersions, and the result was that the number of carbon atoms at the terminal (R3) was preferably 1.

Claims

1. An aqueous composition, characterized in that contain: A block copolymer (A1) represented by the following general formula (1), and water, (X-) a [R1(-W1-R2-W2) b ] m (-R1(-X) c ) p …(1) In the formula (1), X is independently a carboxyl group or a salt thereof, or Y, and Y is R3-(OR4) n -Z-, R1 is independently a divalent and / or trivalent hydrocarbon group having 2 to 52 carbon atoms, R2 is a divalent hydrocarbon group having 2 to 36 carbon atoms, R3 is a hydrocarbon group having 1 to 22 carbon atoms, R4 is a divalent hydrocarbon group having 2 to 4 carbon atoms, W1 and W2 are secondary amide bonds, Z is an ester bond or an amide bond, a is an integer of 1 to 11, b is 1 or 2, c is 1 or 2, m is an integer of 0 to 10, n is an integer of 2 to 100, and p is an integer of 1 to 11, Of all X in the block copolymer (A1) represented by the formula (1), X as Y accounts for 5 mol% or more, The mass ratio of the block copolymer (A1) to water, that is, A1 / water, is 5 / 95 to 50 / 50.

2. The aqueous composition according to claim 1, characterized in that contain: The block copolymer (A1) is characterized in that at least a part of X in the formula (1) is a carboxyl group or a salt thereof.

3. The aqueous composition according to claim 2, characterized in that The amount of X, which is a carboxyl group or a salt thereof, is 30 mol% or more based on the entire amount of X in the block copolymer (A1) contained in the aqueous composition.

4. The aqueous composition according to claim 1, characterized in that The remaining mass after removing the Y portion from all the block copolymers (A1) contained in the aqueous composition is 50% by mass or more and 90% by mass or less based on the total mass of the block copolymer (A1).

5. The aqueous composition according to claim 1, characterized in that The acid value of the block copolymer (A1) is 15 or more and 80 or less.

6. The aqueous composition according to claim 1, characterized in that In the formula (1), 50 mol % or more of either or both of R1 and R2 are divalent hydrocarbon groups having 34 or more carbon atoms.

7. The aqueous composition according to claim 1, characterized in that In the formula (1), at least a portion of X is Y, and R4 has 2 carbon atoms (OR4) n The mass of the site is 5 mass % or more and 45 mass % or less based on the mass of the entire block copolymer (A1).

8. The aqueous composition according to claim 1, characterized in that It further contains a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), <h2 style=";text-align:left;direction:ltr">R5-(OR6)<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> -OR7…(2) In the formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100. At least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5 mass% or more and 50 mass% or less relative to the total mass of the block copolymer (A1) and the polyether (B1).

9. The aqueous composition according to claim 1, characterized in that It further contains a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), <h2 style=";text-align:left;direction:ltr">R5-(OR6)<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> -OR7…(2) In the formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100. At least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 5 mass % or more and 50 mass % or less relative to the total mass of the nonvolatile content in the aqueous composition.

10. The aqueous composition according to claim 1, characterized in that contain: The block copolymer (A1) wherein all Xs in the formula (1) are Ys.

11. The aqueous composition according to claim 10, characterized in that Among X in the block copolymer (A1) represented by the above formula (1), X as Y accounts for 80 mol% or more.

12. The aqueous composition according to claim 1, characterized in that It further contains a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), <h2 style=";text-align:left;direction:ltr">R5-(OR6)<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> -OR7…(2) In the formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100. The acid value of the mixture of the block copolymer (A1) and the polyether (B1) is 10 or less.

13. The aqueous composition according to claim 1, characterized in that The number of carbon atoms of R3 in the formula (1) is 1 to 4.

14. The aqueous composition according to claim 1, characterized in that The block copolymer (A1) in the formula (1) where m=0 is 50% by mass or less based on the total mass of the block copolymer (A1) contained in the aqueous composition.

15. The aqueous composition according to claim 1, characterized in that It further contains a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), <h2 style=";text-align:left;direction:ltr">R5-(OR6)<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> -OR7…(2) In the formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100. At least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 50% by mass or more and 90% by mass or less based on the total mass of the block copolymer (A1) and the polyether (B1).

16. The aqueous composition according to claim 1, characterized in that It further contains a polyether (B1) having a boiling point of 230° C. or higher represented by the following general formula (2), <h2 style=";text-align:left;direction:ltr">R5-(OR6)<h2 style=";text-align:left;direction:ltr"> q <h2 style=";text-align:left;direction:ltr"> -OR7…(2) In the formula (2), R5 is a hydrocarbon group having 1 to 22 carbon atoms, R6 is a divalent hydrocarbon group having 2 to 4 carbon atoms, R7 is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and q is an integer of 2 to 100. At least a portion of X in the formula (1) is Y, and R4 in the block copolymer (A1) has 2 carbon atoms (OR4) n site, and the carbon number of R6 in the polyether (B1) is 2 (OR6) q The total mass of the sites is 50 mass % or more and 90 mass % or less relative to the total mass of the nonvolatile content in the aqueous composition.

17. A diluted composition obtained by diluting the aqueous composition according to any one of claims 1 to 16, characterized in that: The mass ratio of the block copolymer (A1) to water, i.e., A1 / water, is 0.01 / 99.99 to 5 / 95.

18. The dilution composition according to claim 17, characterized in that The present invention further contains at least one viscosity modifier which is different from the block copolymer (A1) and is selected from the group consisting of urethane viscosity modifiers, acrylic viscosity modifiers, modified cellulose viscosity modifiers, polysaccharide viscosity modifiers, amide viscosity modifiers, polyamide viscosity modifiers, urea viscosity modifiers, cellulose nanofibers, and inorganic viscosity modifiers.

19. A water-based coating composition, characterized in that: contain: The aqueous composition according to any one of claims 1 to 16; and Glossy pigment.

20. The water-based coating composition according to claim 19, characterized in that: The present invention further contains at least one viscosity modifier which is different from the block copolymer (A1) and is selected from the group consisting of urethane viscosity modifiers, acrylic viscosity modifiers, modified cellulose viscosity modifiers, polysaccharide viscosity modifiers, amide viscosity modifiers, polyamide viscosity modifiers, urea viscosity modifiers, cellulose nanofibers, and inorganic viscosity modifiers.

Citation Information

Patent Citations

  • Suspending agent for aqueous coating material

    JP1998310726A

  • Method for producing glycol ether having controlled lower odor

    JP2002212125A

  • Hydrocarbon-terminated polyether polyamide block copolymers and uses thereof

    JP2004518006A

  • Water-based Anti-settling agent

    JP2012111832A

  • Viscosity modifier for aqueous resin, and aqueous paint composition

    WO2022097747A1